Fluorinated elastomers for brain probes and other applications
Patent Information
- Application Number
- JP2023555362
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-17
- Filing Date
- 2022-03-09
- Publication Date
- 2025-03-14
AI Technical Summary
Existing microelectrode array techniques for brain-machine interfaces face limitations in increasing sensor density due to mechanical mismatch with brain tissue, leading to immune responses and degradation under physiological conditions, hindering long-term stable mapping of brain activity.
Development of multilayer articles comprising fluorinated polymers, particularly perfluoropolymers, with improved mechanical properties and stability, allowing for high electrode density and reduced ion transport, achieved through plasma treatment and crosslinking to enhance deposition and durability.
The fluorinated polymers exhibit long-term stability and reduced degradation, enabling a 10-fold increase in electrode density with minimal impedance change, facilitating stable neural signal recording over extended periods.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] Related Applications This application claims priority to U.S. Provisional Application No. 63 / 159,623, filed on March 11, 2021, and entitled "Perfluorinated Elastomers for Brain Probes and Other Applications," and U.S. Provisional Application No. 63 / 290,732, filed on December 17, 2021, and entitled "Fluorinated Elastomers for Brain Probes and Other Applications," each of which is incorporated by reference in its entirety herein for all purposes.
[0002] SUMMARY OF THE DISCLOSURE Articles and methods relating to fluorinated elastomers are generally described. [Background technology]
[0003] Decoding neural signals is of fundamental importance to bridge the knowledge gap that exists between the molecular understanding of synaptic circuits and behavioral neuroscience. Understanding neurodegenerative diseases or brain circuits in general, increasing the bandwidth of brain-machine interfaces for new medical devices such as neuroprostheses or deep brain stimulators, to name a few, are potential applications that would benefit from advanced neural interfacing technologies. However, to investigate the dynamics of neural networks on sufficiently large spatial and temporal scales to understand neural coding, simultaneous measurements of tens or hundreds of thousands of neurons in vivo over time are required. Moreover, each neuron has tens or hundreds of thousands of synaptic connections, which may span the entire brain volume. Therefore, long-term stable whole-brain activity mapping is necessary to understand the brain connectome.
[0004] Various microelectrode array technologies have been developed to allow the measurement of single-unit extracellular action potentials of hundreds to thousands of neurons simultaneously over periods ranging from weeks to months. However, further increasing the density of electrical sensors such as microelectrodes and transistors has been limited by immune reactions due to mechanical mismatch between the probe and brain tissue. Improvements are therefore needed. Summary of the Invention
[0005] Articles and methods relating to fluorinated elastomers are generally described. The subject matter of the present invention includes, in some cases, interrelated products, alternative solutions to a particular problem, and / or a plurality of different applications of one or more systems and / or articles.
[0006] One aspect is generally directed to an article. According to some embodiments, the article includes: a first layer comprising a first fluorinated polymer; a second layer bonded to the first layer; and a third layer comprising a second fluorinated polymer and bonded to the second layer.
[0007] Another aspect is generally directed to an article, according to some embodiments: a substrate adapted to be implanted into an organ of a subject, the substrate comprising a plurality of electrodes, the substrate comprising a first layer comprising a first fluorinated polymer, a second layer bonded to the first layer, and a third layer comprising a second fluorinated polymer bonded to the second layer.
[0008] Yet another aspect is generally directed to articles. In some embodiments, the article includes: a substrate including a plurality of electrodes, the substrate including a first layer including a first fluorinated polymer, a second layer bonded to the first layer, and a third layer including a second fluorinated polymer bonded to the second layer; -9 Electrode / micron 2 and a base material having the above ratio.
[0009] Yet another aspect is generally directed to articles. In some embodiments, the article includes: a substrate comprising a plurality of electrodes, the substrate comprising a first layer comprising a first fluorinated polymer, a second layer bonded to the first layer, and a third layer comprising a second fluorinated polymer bonded to the second layer, the electrodes being 10 -3 Electrode / micron 2 It has a number density of more than 1000.
[0010] Another embodiment is generally directed to an article. In some embodiments, the article is a substrate comprising a plurality of electrodes, the substrate comprising a first layer comprising a first fluorinated polymer, a second layer bonded to the first layer, and a third layer comprising a second fluorinated polymer bonded to the second layer, the substrate comprising a first fluorinated polymer and a second fluorinated polymer. 6 It has a total modulus of elasticity of less than 1 Pa.
[0011] Yet another aspect is generally directed to an article. According to some embodiments, the article includes: a first layer comprising a first fluorinated polymer; a second layer bonded to the first layer; and a third layer bonded to the second layer comprising a second fluorinated polymer; the third layer has an average thickness H in microns, and the polymer on the substrate exhibits a reduction in specific electrochemical impedance modulus, i.e., at least 1*H. 2 After immersion in a 10x PBS solution at 65°C for days, the electrochemical impedance modulus at 1 kHz (electrochemical impedance modulus normalized to the shape of the sample) is 50% or less.
[0012] One embodiment is generally directed to an article comprising: a first layer comprising a perfluoropolyether; a second layer bonded to the first layer; and a third layer bonded to the second layer comprising a perfluoropolyether.
[0013] Another embodiment is generally directed to an article that includes a perfluoropolyether having a weight average molecular weight of less than 8 kDa, where the perfluoropolyether is on a semiconductor substrate.
[0014] Yet another embodiment is generally directed to an article comprising a polymer comprising a crosslinked perfluoropolyether in a substrate, the polymer being formed into an article having a minimum dimension of at least 0.3 micrometers that is immersed in 1,3-bis(trifluoromethyl)benzene for 9 seconds or more, dried in nitrogen, and has a minimum dimension of at least 10 micrometers when measured at 1 kHz. 6 The specific electrochemical impedance modulus in Ω·m is shown.
[0015] Yet another aspect is generally directed to an article comprising a polymer comprising a crosslinked perfluoropolyether on a substrate, wherein the polymer on the substrate exhibits a 50% or less decrease in specific electrochemical impedance modulus at 1 kHz after immersion in a phosphate buffer for 100 days.
[0016] Another aspect is generally directed to a method, in some embodiments, comprising inserting into an organ of a subject a substrate comprising a plurality of electrodes, the substrate comprising a first layer comprising a first fluorinated polymer, a second layer bonded to the first layer, and a third layer comprising a second fluorinated polymer bonded to the second layer.
[0017] Yet another aspect is generally directed to a method. In some embodiments, the method includes depositing a fluorinated polymer on a substrate; applying an inert gas plasma to the fluorinated polymer to form a treated fluorinated polymer; and depositing a material on the treated fluorinated polymer.
[0018] Yet another aspect is generally directed to a method. In some embodiments, the method includes depositing a fluorinated polymer on a substrate, treating the fluorinated polymer to render it amenable to deposition, and depositing a second fluorinated polymer on the treated fluorinated polymer.
[0019] One aspect is generally directed to a method. In some embodiments, the method includes depositing a fluorinated polymer on a substrate; treating the fluorinated polymer to render it more amenable to deposition; and depositing a material forming a plurality of electrodes on the treated fluorinated polymer.
[0020] Another aspect is generally directed to a method. In some embodiments, the method includes: determining electrical signals from a plurality of electrodes of a substrate at least partially contained within a subject, the substrate including a first layer comprising a first fluorinated polymer, a second layer bonded to the first layer, and a third layer comprising a second fluorinated polymer bonded to the second layer.
[0021] Yet another aspect is generally directed to a method. In some embodiments, the method includes: determining the electrical activity of a single cell in a living subject using electrodes of a substrate that is in contact with the cell for at least five days, wherein the substrate includes a layer that includes a fluorinated polymer.
[0022] Yet another aspect is generally directed to a method. In some embodiments, the method includes: determining electrical signals from a plurality of electrodes of a substrate at least partially contained within an object, the substrate being 10 6 The laminate has an overall elastic modulus of less than or equal to 10 Pa and includes a layer that includes a fluorinated polymer.
[0023] One aspect is generally directed to a method. In some embodiments, the method includes: electrically stimulating cells in a subject with a plurality of electrodes of a substrate, the substrate including a first layer comprising a fluorinated polymer, a second layer bonded to the first layer, and a third layer comprising a fluorinated polymer bonded to the second layer.
[0024] Another embodiment includes depositing a perfluoropolyether on a substrate; subjecting the perfluoropolyether to an argon plasma to form a treated perfluoropolyether; and depositing a material on the treated perfluoropolyether.
[0025] Other advantages and novel features of the present invention will become apparent from the following detailed description of various non-limiting embodiments of the invention when considered in conjunction with the accompanying figures. In the event that the present specification and a document incorporated by reference include conflicting and / or inconsistent disclosure, the present specification shall control. [Brief description of the drawings]
[0026] Non-limiting embodiments of the present invention are illustratively described with reference to the accompanying figures, which are schematic and are not intended to be drawn to scale unless otherwise indicated. In the figures, each identical or nearly identical component shown is typically represented by a single numeral. Also, for clarity, not every component is shown in every figure, and not every component of each embodiment of the present invention is shown, unless illustration is necessary for those skilled in the art to understand the invention.
[0027] [Figure 1] FIG. 1 shows a cross-sectional schematic of an exemplary article comprising a perfluoropolymer, according to certain embodiments. [Diagram 2] FIG. 2 is a cross-sectional schematic diagram of an experimental setup for measuring impedance, according to certain embodiments. [Diagram 3] FIG. 3 illustrates a method of preparing an article comprising a perfluoropolymer, according to certain embodiments. [Figure 4A] FIG. 4A shows specific electrochemical impedance measurements of a polymer film according to certain embodiments. [Figure 4B] FIG. 4B shows specific electrochemical impedance measurements of a polymer film according to certain embodiments. [Figure 4C] FIG. 4C shows specific electrochemical impedance measurements of a polymer film according to certain embodiments. [Figure 4D] FIG. 4D shows specific electrochemical impedance measurements of a polymer film according to certain embodiments. [Figure 5A] FIG. 5A illustrates a method for determining ion concentration of a polymer, according to certain embodiments. [Figure 5B] FIG. 5B shows an exemplary concentration profile of ions after exposing the polymer, previously equilibrated with buffer, to deionized water. [Figure 5C] FIG. 5C compares ion desorption of a polymer layer at various temperatures, according to certain embodiments. [Figure 5D] FIG. 5D compares ion desorption of a polymer layer at various temperatures, according to certain embodiments. [Figure 5E] FIG. 5E compares the ionic conductivity of polymer layers determined by different measurements, according to certain embodiments. [Figure 6] FIG. 6 shows the equation used to determine ionic conductivity, according to certain embodiments. [Figure 7A] FIG. 7A compares the temperature dependence of ion behavior within a polymer, according to certain embodiments. [Figure 7B] FIG. 7B compares the temperature dependence of ion behavior within a polymer, according to certain embodiments. [Figure 7C] FIG. 7C compares the temperature dependence of ion behavior within a polymer, according to certain embodiments. [Figure 8]FIG. 8 illustrates an exemplary method of preparing an article including a perfluoropolymer, according to certain embodiments. [Figure 9A] FIG. 9A illustrates an exemplary nitrogen diffuser in accordance with certain embodiments. [Figure 9B] FIG. 9B illustrates an exemplary nitrogen diffuser in accordance with certain embodiments. [Figure 10A] FIG. 10A compares the specific electrochemical impedance modulus of polymers according to certain embodiments. [Figure 10B] FIG. 10B shows the mechanical properties of a polymer according to certain embodiments: [Figure 10C] FIG. 10C compares the elastic modulus and electrochemical stability of polymeric materials, according to certain embodiments. [Figure 11A] FIG. 11A is an exploded perspective view of an exemplary article designed for use as a neural sensor, according to certain embodiments. [Figure 11B] FIG. 11B shows an image of an exemplary article designed for use as a neural sensor, according to certain embodiments. [Figure 11C] FIG. 11C shows an image of an exemplary article designed for use as a neural sensor, according to certain embodiments. [Figure 11D] FIG. 11D shows an image of an exemplary article designed for use as a neural sensor, according to certain embodiments. [Figure 11E] FIG. 11E shows an image of an exemplary article designed for use as a neural sensor, according to certain embodiments. [Figure 12A] FIG. 12A shows the resistance of a metal electrode according to certain embodiments. [Figure 12B] FIG. 12B shows the resistance of a metal electrode according to certain embodiments. [Figure 13A] FIG. 13A compares the impedance behavior of articles including uncompensated electrodes and PEDOT:PSS coated electrodes, according to certain embodiments. [Figure 13B]FIG. 13B compares the impedance behavior of articles including uncompensated electrodes and PEDOT:PSS coated electrodes, according to certain embodiments. [Figure 14] FIG. 14 shows a photograph of a plastic frame used to hold the device, according to certain embodiments. [Figure 15A] FIG. 15A shows the insertion of a device into the brain of a live, moving mouse, according to certain embodiments. [Figure 15B] FIG. 15B shows the insertion of a device into the brain of a live, moving mouse, according to certain embodiments. [Figure 16A] FIG. 16A shows the signal collected from the device implanted in the brain of a living mouse. [Figure 16B] FIG. 16B shows the signal collected from the device implanted in the brain of a living mouse. [Figure 16C] FIG. 16C shows the signal collected from the device implanted in the brain of a living mouse. [Figure 16D] FIG. 16D shows the signal collected from the device implanted in the brain of a live mouse. [Figure 16E] FIG. 16E shows the signal collected from the device implanted in the brain of a live mouse. [Figure 17A] FIG. 17A shows specific electrochemical impedance measurements of a polymer film, according to certain embodiments. [Figure 17B] FIG. 17B shows specific electrochemical impedance measurements of a polymer film, according to certain embodiments. [Figure 17C] FIG. 17C shows specific electrochemical impedance measurements of polymer films, according to certain embodiments. [Figure 18] FIG. 18 illustrates a method of preparing an article comprising a fluorinated polymer, according to certain embodiments. [Figure 19] FIG. 19 shows an image of an exemplary article designed for use as a neural sensor, according to certain embodiments. [Figure 20]FIG. 20 shows the change in electrochemical impedance modulus of an electrode upon coating with a conductive material, according to some embodiments. [Figure 21] FIG. 21 shows the electrochemical impedance modulus over time of a polymer on an exemplary electrode, according to some embodiments. [Figure 22] FIG. 22, according to some embodiments, compares electrode number density and elastic modulus for various neural sensors using neural sensors prepared according to embodiments described herein. [Figure 23] FIG. 23 shows a schematic of an exemplary peel test, according to some embodiments. [Figure 24] FIG. 24 shows the bond energy of polymer layers at various peel rates, according to certain embodiments. [Diagram 25] FIG. 25 illustrates the interconnect resistance of an exemplary brain probe, in accordance with certain embodiments. [Figure 26] FIG. 26 is a schematic cross-sectional view of a multi-layer article according to certain embodiments. [Figure 27] FIG. 27 illustrates an exemplary bending stiffness of a simulated multi-layer article, according to certain embodiments. [Figure 28] FIG. 28 shows the ratio between the bending stiffness of different exemplary multi-layer articles as a function of the number of metal layers, according to certain embodiments. [Figure 29A] FIG. 29A illustrates implantation of an exemplary neural sensor substrate, according to some embodiments. [Figure 29B] FIG. 29B illustrates implantation of an exemplary neural sensor substrate, according to some embodiments. [Diagram 30] FIG. 30 shows exemplary measurements using multiple exemplary electrodes implanted in a subject's brain, according to some embodiments. [Diagram 31] FIG. 31 shows exemplary results of a spike sorting analysis performed on measurements made with multiple exemplary electrodes implanted in a subject's brain, according to some embodiments. [Diagram 32]FIG. 32 illustrates an example mapping of measurements using multiple example electrodes, where the measurements are represented according to principal component space, in accordance with certain embodiments. [Figure 33A] FIG. 33A shows average electrode-associated noise over a 10-week period following implantation of an exemplary sensor into a subject's brain, in accordance with certain embodiments. [Figure 33B] FIG. 33B shows spike amplitude averaged across all channels of an electrode over a 10-week period following implantation of an exemplary sensor into a subject's brain, in accordance with certain embodiments. [Diagram 34] FIG. 34 shows exemplary fluorescence measurements of a subject's immune response to an implanted brain probe, according to certain embodiments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] Large-scale brain-wide neuronal activity mapping is important for deciphering neuronal population dynamics in neuroscience, understanding and mitigating neurological diseases, and building wideband BMIs for neural prostheses and communication. Ultimately, brain mapping aims to simultaneously record the activity of millions, if not billions, of neurons in a long-term, stable manner with single-cell, millisecond spatiotemporal resolution. “Tissue-like” thin-film electronics with subcellular size and tissue-level flexibility could enable glioma-free implantation and record stable neuronal activity with single-cell, single-spike spatiotemporal resolution over time for applications in neuroscience, bioelectronic medicine, and brain-machine interfaces (BMIs). One major challenge is to scale up the number of microelectrodes for tissue-like electronics without using rigid materials that are fundamentally mismatched to the mechanical properties of the brain. Another challenge is that soft electronics are prone to degradation in the chemical environment of the brain, where most polymeric materials degrade over time. Articles and sensors containing fluorinated polymers offer significant advantages for electronic devices such as neural implants. For example, fluorinated polymers have desirable electrical and mechanical properties for brain implants and may exhibit excellent long-term stability under physiological conditions.
[0029] The present disclosure recognizes the importance of fluorinated polymers for brain implants and provides an inventive method for preparing multi-layer articles that include multiple fluorinated polymer layers. These articles can exhibit some of the superior properties of fluorinated polymers. For example, some exemplary non-limiting articles described herein are 1 micron thick. 2 10 per -3 Electrodes and / or 6 It has an overall elastic modulus of less than 100 Pa. 2 This number of electrodes per micron, according to some embodiments, represents a 10-fold increase in the area number density of electrodes compared to sensors having a comparable elastic modulus. Furthermore, this elastic modulus, according to some embodiments, represents a 10-fold increase in the area number density of electrodes compared to sensors having a comparable elastic modulus. 2This corresponds to one thousandth of the elastic modulus of a brain sensor with a comparable number of electrodes per sensor.
[0030] Nanofabrication techniques can be used to fabricate bioelectronics for use in vivo, but the long-term stability of these devices under physiological conditions and the mismatch between their mechanical properties and those of human tissues limit the scope of application of these techniques. In some embodiments, fluorinated polymers (such as perfluoropolymers) have been identified as a way to address these limitations. Thus, the present disclosure, in certain aspects, generally relates to perfluoropolymers with long-term stability under near-physiological conditions that can be used in a variety of articles and devices. For example, in some embodiments, these perfluoropolymers are used in implants, e.g., as coatings. In some embodiments, the present disclosure relates to fluorinated polymers in general, including fluorinated polymers with long-term stability, such as perfluoropolymers. In some embodiments, these fluorinated polymers are used in implants, e.g., as coatings.
[0031] Some aspects of the present disclosure are directed to systems and methods for preparing fluorinated polymers, including articles that include such polymers, such as devices, sensors, implants, circuits, coated substrates, and the like. Additionally, some aspects of the present disclosure are directed to systems and methods for preparing perfluoropolymers, including articles that include such polymers, such as devices, sensors, implants, circuits, coated substrates, and the like. Without wishing to be bound by any theory, it is believed that the superhydrophobicity of perfluoropolymers can make the fabrication of articles and devices that include perfluoropolymers difficult. Thus, in one embodiment, the present disclosure is directed to a method for treating perfluoropolymers (e.g., perfluoropolyethers) that unexpectedly allows for the deposition of additional materials bonded to the perfluoropolymer. The perfluoropolymers can be treated by applying a plasma (e.g., argon plasma) to the perfluoropolymer. The additional materials are additional perfluoropolymers that can, in some cases, increase the overall thickness of the perfluoropolymer layer. Thus, in some embodiments, the fabrication of surprisingly thick (e.g., thicker than 300 nanometers) perfluoropolymer layers is disclosed. This surprising thickness may beneficially improve the stability and / or mechanical properties of perfluoropolymers in electronics. In contrast, other techniques are unable to fabricate such thick perfluoropolymer layers on articles or devices.
[0032] In certain aspects, the disclosure is directed to articles and / or devices that include fluorinated polymers. Here, one non-limiting example is provided for illustrative purposes. Other embodiments are possible, as described in more detail below. In certain aspects, the disclosure is directed to articles and / or devices that include perfluoropolymers. For example, some embodiments are directed to making articles with perfluoropolymers. For example, the article can have a first layer of perfluoropolymer (e.g., perfluoropolyether), a second layer (e.g., aluminum, gold, etc.) bonded to the first layer, and a third layer of perfluoropolymer (e.g., perfluoropolyether) bonded to the third layer. For example, FIG. 1 presents an article 100 having a first layer 102 of perfluoropolymer, a second layer 104 bonded to the first layer 102, and a third layer 106 of perfluoropolymer bonded to the second layer 104. Such articles may cover at least a portion of an electronic circuit or other applications as described herein. In some cases, such articles and circuits may prove useful as components of bioelectronic devices.As noted above, layered perfluoropolymers have not previously been described.
[0033] However, it should be understood that these examples are given by way of illustration and not by way of limitation.
[0034] Certain aspects of the present disclosure are directed to polymers, particularly perfluoropolymers. According to certain embodiments, the polymer is a fluorinated polymer. For example, the polymer may be a perfluoropolymer, e.g., a polymer in which carbon atoms within a portion of the polymer are bonded only to fluorine and / or other heteroatoms, rather than to hydrogen. The polymer may also be a fluorinated but non-perfluoropolymer, as described in more detail below. In some embodiments, the polymer comprises or consists essentially of a perfluoropolyether. The polymer may be any suitable perfluoropolyether. For example, the polymer may comprise perfluoropolyether (PFPE), polytetrafluoroethylene (PTFE), perfluoropolyether dimethyl acrylate (PFPE-DMA), fluorinated ethylene propylene (FEP), perfluoroalkoxy polymer (PFA), or polychlorotrifluoroethylene (PCTFE). The polymer may be a copolymer, such as tetrafluoroethylene propylene (TFE). For example, in some embodiments, the polymer is perfluoropolyether dimethyl acrylate.
[0035] Articles and devices comprising perfluoropolymers, as well as methods for preparing perfluoropolymers, are generally described. In some cases, such perfluoroelastomers can be used, for example, for sensing neural activity by encapsulating electronic circuits, or for other applications. Furthermore, according to certain embodiments, surprisingly, polymers can be directly deposited onto layers comprising low molecular weight perfluoropolymers, for example, without swelling in the presence of certain solvents. Some embodiments are generally directed to devices and methods for processing perfluoropolymers and subsequently depositing materials onto the processed perfluoropolymers. It is believed that this allows for the creation and patterning of multilayer articles comprising perfluoroelastomers.
[0036] Such polymers can reduce or inhibit the passage of ions therethrough in various applications, such as implants. For example, perfluoropolymers can be present in at least a portion of the substrate of an article or device. As discussed herein, such perfluoropolymers can be used in certain embodiments to inhibit the passage of ions in various articles or devices, such as devices implanted in a subject or exposed to physiological conditions. For such polymers, degradation can be quantified by measuring the specific electrochemical impedance modulus (i.e., the electrochemical impedance modulus normalized to the geometry of the sample) over an extended period of time, such as during exposure to physiological conditions. For example, in one assay, such polymer films having a thickness of 1 μm or less can surprisingly retain a large portion (e.g., 50% or more) of their specific electrochemical impedance modulus even after immersion in phosphate buffer for 100 days or more.
[0037] Without wishing to be bound by any theory, it is believed that the hydrophobicity of perfluoropolymers may make the manufacture of articles and devices containing perfluoropolymers difficult. Thus, in one embodiment, the present disclosure is directed to a method of treating perfluoropolymers (e.g., perfluoropolyethers) that unexpectedly allows for the deposition of additional materials bonded to the perfluoropolymer. The perfluoropolymers can be treated by applying a plasma (e.g., argon plasma) to the perfluoropolymer. The additional materials are additional perfluoropolymers that can potentially increase the overall thickness of the perfluoropolymer layer. Thus, in some embodiments, the creation of surprisingly thick (e.g., thicker than 300 nanometers) perfluoropolymer layers is disclosed. For example, polymer layers thicker than 3 micrometers can be created. This surprising thickness may beneficially improve the stability and / or mechanical properties of perfluoropolymers in electronics. In contrast, other techniques are unable to create such thick perfluoropolymer layers on articles and devices.
[0038] In another embodiment, specific properties of perfluoropolymers are controlled by crosslinking the perfluoropolymers. This control of properties can beneficially improve the performance of perfluoropolymers as components of articles and devices in some embodiments. For example, properties such as electrical properties or reduced ion transport can be achieved using specific crosslinked polymers, for example as described herein. However, it should be understood that crosslinking is not a requirement in all embodiments.
[0039] In some embodiments, the polymer is a fluorinated polymer that is not perfluorinated. For example, the fluorinated polymer may be a partially fluorinated polymer. In some embodiments, the fluorinated polymer is 25% or more, 50% or more, 75% or more fluorinated. In some embodiments, the fluorinated polymer is 100% or less, 90% or less, 75% or less, 50% or less, or less fluorinated. Combinations of these ranges are also possible. For example, in some embodiments, the fluorinated polymer is 25% or more, 100% or less fluorinated.
[0040] The polymer may be any of a variety of suitable fluorinated polymers. For example, in some embodiments, the polymer may be poly(1,1,1,3,3,3-hexafluoroisopropyl acrylate) (PHFIPA) or poly[2-(perfluorohexyl)ethyl]acrylate (PPFHEA). The polymer may also be a copolymer (e.g., between two or more fluorinated polymers, including both these polymers and the perfluoropolymers described above).
[0041] In the context of the present disclosure, it has been recognized that fluorinated polymers are difficult to process, which can adversely affect the use of fluorinated polymers. Accordingly, certain aspects are directed to improved processing of fluorinated polymers, such as perfluoropolymers. For example, according to some embodiments, fluorinated polymers can be coated and photopatterned onto a substrate or other polymer layer, for example, using added spacers and / or nitrogen diffusing agents. In some embodiments, materials can be deposited on the fluorinated polymer, such as by treating the fluorinated polymer, which can promote bonding between the fluorinated polymer and the subsequently deposited material.
[0042] The deposition of materials onto the fluorinated polymer layer is, in some embodiments, important for making relatively thick and / or multi-layer articles comprising fluorinated polymers (e.g., perfluoropolymers), as discussed herein. In some embodiments, the fluorinated polymer may be treated. For example, some embodiments include applying a plasma (e.g., argon plasma) to the fluorinated polymer to form a treated fluorinated polymer, as described in more detail below. It has been surprisingly recognized that the treatment of the fluorinated polymer may, in some embodiments, advantageously facilitate the deposition of materials onto the surface of the fluorinated polymer.
[0043] In particular, the present disclosure is directed to the processing of perfluoropolymers in certain embodiments. It is recognized that perfluoropolymers can be difficult to process, which can have a detrimental effect on the use of perfluoropolymers. Thus, certain aspects are directed to improved perfluoropolymers. For example, according to some embodiments, perfluoropolymers can be coated onto substrates or other polymer layers, for example, using added spacers and / or nitrogen diffusion agents. In some embodiments, materials can be deposited onto perfluoropolymers (e.g., perfluoropolyethers), for example, by treating the perfluoropolymer, which can promote bonding between the perfluoropolymer and the subsequently deposited material.
[0044] The deposition of material onto the perfluoropolymer layer is important in some embodiments for making relatively thick and / or multi-layer articles comprising perfluoropolymer, for example as discussed herein. In some embodiments, for example, the perfluoropolymer may be treated. For example, some embodiments include applying a plasma (e.g., argon plasma) to the perfluoropolymer (e.g., perfluoropolyether) to form a treated perfluoropolymer (e.g., perfluoropolyether), as described in more detail below. It has been surprisingly recognized that the treatment of the perfluoropolymer can advantageously promote the deposition of material onto the surface of the perfluoropolymer in some embodiments.
[0045] Some embodiments are generally directed to relatively thick and / or multi-layer articles that may be resistant to degradation. For example, in certain embodiments, thick and / or multi-layer articles may be used in implantable devices. In some cases, such articles may be resistant to degradation by aqueous solutions.
[0046] For example, the polymer and / or article comprising the polymer can be immersed in an aqueous solvent (e.g., saline) for a period of time. Certain polymers and / or articles comprising the polymer as discussed herein can retain a high specific electrochemical impedance modulus when immersed in an aqueous solvent, which can be used to indicate that the polymer and / or article can partially or completely inhibit the transport of ions therethrough.
[0047] Without wishing to be bound by theory, the reduction of ion transport in a polymer can result in a substantial reduction in ion conductivity through the polymer, which, according to certain embodiments, can reduce degradation and improve the dielectric properties of the polymer. In some embodiments, the polymer (e.g., perfluoropolymer) undergoes a phase transition at a phase transition temperature. For example, according to certain embodiments, the polymer (e.g., perfluoropolyether) constitutes a more crystalline phase at lower temperatures. Without wishing to be bound by theory, the ion transport can be greater in the phase found at a temperature higher than the phase transition temperature. Certain polymers as discussed herein undergo a phase transition temperature near physiological temperatures (e.g., within ±1°C, ±2°C, ±3°C, ±5°C of 37°C). The presence of a phase transition near physiological temperatures can, according to certain embodiments, be associated with a reduction in ion transport through the polymer under physiological conditions.
[0048] In some cases, a high specific electrochemical impedance modulus may indicate that the polymer and / or article comprising the polymer is more stable in vivo. This may be determined, according to certain embodiments, by immersing the polymer and / or article comprising the polymer in an aqueous solution (e.g., phosphate buffer) for a period of time; according to some embodiments, the polymer may experience only a small decrease in specific electrochemical impedance modulus even after being immersed for an extended period of time, for example, for at least 100 days, or other times as discussed herein.
[0049] For example, according to certain embodiments, the polymer, when formed into an article, has a solubility of 1×10 6 Ω m or more, 2×10 6 Ω m or more, 3×10 6 Ω m or more, 5×10 6The polymer exhibits a specific electrochemical impedance modulus of Ω·m or more. According to certain embodiments, the polymer, when formed into an article, exhibits a specific electrochemical impedance modulus of 25% or more, 50% or more, 75% or more, 90% or more, 95% or more, or 99% or more of its original specific electrochemical impedance modulus after immersion in an aqueous medium. In other words, an article including the polymer may exhibit a small decrease in specific electrochemical impedance modulus even after immersion in an aqueous medium for a period of time, which may indicate that the polymer and / or the article can inhibit ion transport. For example, according to certain embodiments, an article including the polymer may exhibit a decrease in specific electrochemical impedance modulus of 75% or less, 50% or less, 25% or less, 10% or less, 5% or less, 1% or less, etc. of its original specific electrochemical impedance modulus after immersion in an aqueous medium for a period of time, e.g., at least 100 days, or other time as discussed herein.
[0050] In general, electrical impedance can be expressed as a complex quantity, as known to those skilled in the art. For example, electrochemical impedance can be described as having an electrochemical impedance modulus (magnitude of electrical impedance) and a phase (phase angle of a complex number). The electrochemical impedance modulus is geometry dependent and can be normalized by the geometry of the sample to generate a specific electrochemical impedance modulus. For example, in an embodiment including a homogeneous polymer having an area and thickness, the specific electrochemical impedance modulus of the homogeneous polymer is the electrochemical impedance modulus of the homogeneous polymer multiplied by the area of the polymer divided by the thickness of the polymer. Normalization allows comparison between samples of different geometries. According to certain embodiments, the area of the polymer is known. For example, in certain embodiments, the area of the polymer used to calculate the specific electrochemical impedance modulus may be equal to the area of a conductive material disposed under the polymer. The thickness of the polymer can be determined by any suitable technique, such as, for example, a stylus profiler, a scanning electron microscope, an atomic force microscope, an x-ray reflectometer, etc.
[0051] Electrochemical impedance is usually measured at a frequency. For example, in some embodiments, electrochemical impedance is measured at 1 kHz, 2 kHz, 5 kHz, or 10 kHz. Electrochemical impedance can be measured by any suitable technique. For example, a person skilled in the art will know that electrochemical impedance can be measured using a standard three-electrode setup as shown in FIG. 2. An exemplary procedure for measuring electrical impedance is described in Example 2 below.
[0052] According to certain embodiments, the aqueous solvent comprises a phosphate buffer. In some embodiments, the phosphate buffer (PBS) has a concentration of 0.5 times, 1 times, 2 times, 3 times, 5 times, 8 times, or 10 times or more of the standard concentration of PBS (0.1M). In some embodiments, the phosphate buffer (PBS) has a concentration of 15 times, 12 times, 10 times, 8 times, 5 times, or 3 times or less of the standard concentration of PBS (0.1M). Here, a solution of phosphate buffer that is 10 times the standard concentration of PBS is referred to as 10 times phosphate buffer or 10 times PBS. Combinations of these ranges are possible. For example, according to certain embodiments, the phosphate buffer has a concentration of 0.5 times or more and 15 times or less. According to certain embodiments, the aqueous solution is 1 times PBS. In some embodiments, the aqueous solution is 10 times PBS.
[0053] In some embodiments, the immersion is performed at a temperature. According to certain embodiments, the immersion temperature is 20°C or more, 25°C or more, 30°C or more, 35°C or more, 37°C or more, 40°C or more, 45°C or more, 50°C or more, 60°C or more, 70°C or more, or more than 70°C. According to certain embodiments, the immersion temperature is 90°C or less, 80°C or less, 70°C or less, 60°C or less, 50°C or less, 40°C or less, 37°C or less, or less than 37°C. Combinations of these ranges are also possible. For example, according to certain embodiments, the immersion temperature is 20°C or more and 90°C or less.
[0054] The polymer, according to some embodiments, may experience a small decrease in specific electrochemical impedance modulus, e.g., less than 5%, or other decrease as described herein, after immersion in an aqueous solvent for a period of time. For example, the polymer may experience a slight decrease in specific electrochemical impedance modulus after immersion for 5 days or more, 6 days or more, 7 days or more, 8 days or more, 9 days or more, 10 days or more, 15 days or more, 25 days or more, 50 days or more, 100 days or more, 150 days or more, 200 days or more, 250 days or more, 300 days or more, 350 days or more, 400 days or more, 450 days or more, 500 days or more, or more than 500 days. Combinations of these ranges and the ranges previously mentioned are possible. For example, according to some embodiments, the polymer may exhibit a decrease in specific electrochemical impedance modulus at 1 kHz of 50% or less after immersion in a phosphate buffer solution for 100 days or more. As another example, according to certain embodiments, the polymer exhibits a decrease in specific electrochemical impedance modulus at 1 kHz of 50% or less after immersion in phosphate buffer for 450 days. As yet another example, according to certain embodiments, the polymer exhibits a decrease in specific electrochemical impedance modulus at 1 kHz of 50% or less after immersion in 10x phosphate buffer at 70° C. for 5 days.
[0055] According to some embodiments, the polymer may experience a small decrease in specific electrochemical impedance modulus after being immersed in an aqueous medium for a period of time related to the average thickness H of the polymer in the article (in microns). For example, in some embodiments, the polymer may experience a small decrease in specific electrochemical impedance modulus after being immersed in an aqueous medium for a period of time related to the average thickness H of the polymer in the article (in microns). 2 More than days, 2*H 2 More than days, 3*H 2 More than 4 days, 4*H 2 More than 5 days, 5*H 2 More than days, 10*H 2 After being immersed in an aqueous medium for days or more, the polymer experiences a small decrease in specific electrochemical impedance modulus. In some embodiments, the polymer 2 Less than days, 50*H 2 Less than days, 20*H 2 Less than days, 10*H 2The polymer experiences a small decrease in specific electrochemical impedance modulus after immersion in an aqueous solvent for days or less. Combinations of these ranges are also possible. For example, in some embodiments, the polymer 2 More than days, 100*H 2 After immersion in an aqueous medium for days or less, the polymer experiences a small decrease in the specific electrochemical impedance modulus. Combinations of these and the ranges previously described are also possible. For example, according to some embodiments, the polymer is immersed in 10x phosphate buffer at 65°C for 1*H. 2 After immersion for more than 1 day, the specific electrochemical impedance modulus at 1 kHz decreases by less than 50%.
[0056] The resistance of a polymer to degradation may be related to crosslinking of the polymer according to certain embodiments. Any suitable crosslinking chemistry may be present in the polymer. Thus, a polymer (e.g., perfluoropolyether) may include a crosslinking agent according to certain embodiments. For example, according to one set of embodiments, perfluoropolyether dimethyl acrylate (PFPE-DMA) includes two methyl acrylate species, each of which may undergo a crosslinking reaction according to certain embodiments. Thus, for example, perfluoropolyether dimethyl acrylate (PFPE-DMA) may be crosslinked via free radical polymerization of the methyl acrylate species of PFPE-DMA, resulting in the formation of a crosslinked network that includes a perfluoropolymer in some embodiments.
[0057] In some embodiments, highly crosslinked perfluoropolymers are more resistant to degradation. Such resistance to degradation can be determined, for example, by exposing the perfluoropolymer to a solvent, such as a fluorinated solvent. The degree of crosslinking can be measured in any suitable manner. In some cases, the degree of crosslinking can be measured directly, for example, by spectroscopically detecting the concentration of crosslinks in the polymer. In other embodiments, the degree of crosslinking can be determined indirectly. For example, in some cases, the degree of crosslinking can be determined by determining the degradation of the polymer in a solvent that can dissolve the polymer when not crosslinked. In general, highly crosslinked polymers are less soluble in a given solvent than less crosslinked polymers.
[0058] According to certain embodiments, the cross-linked polymer is hardly degraded when immersed in a solvent that can dissolve the polymer when not cross-linked. Any solvent that can dissolve the polymer when not cross-linked can be used to determine the degree of cross-linking of the polymer. According to certain embodiments, a fluorinated solvent may be used to determine the cross-linking of a fluorinated polymer. For example, according to certain embodiments, a fluorinated solvent can be used to determine the cross-linking of a perfluoropolymer (e.g., perfluoropolyether). In some embodiments, 1,3-bis(trifluoromethyl)benzene is a suitable solvent for determining the degree of cross-linking of a polymer.
[0059] In some embodiments, the fluorinated polymer has a high specific electrochemical impedance modulus as described above (e.g., at least 10), even after immersion in a solvent as described above. 6 Similarly, in some embodiments, the fluorinated polymer may have a low decrease in specific electrochemical impedance modulus as described above (e.g., a decrease in specific electrochemical impedance modulus of 50% or less) after immersion in a solvent.
[0060] In addition, in some embodiments, the perfluoropolymer has a high specific electrochemical impedance modulus as described above (e.g., at least 10), even after immersion in a solvent as described above. 6 Similarly, in some embodiments, the perfluoropolymer may have a low decrease in specific electrochemical impedance modulus as described above (e.g., a decrease in specific electrochemical impedance modulus of 50% or less) after immersion in a solvent.
[0061] According to some embodiments, crosslinking of a polymer can be determined by measuring the specific electrochemical impedance modulus of the polymer after exposure to a solvent that can dissolve the polymer when not crosslinked. For example, in some embodiments, a more heavily crosslinked polymer exhibits a higher specific electrochemical impedance modulus when first formed into an article and then immersed in a fluorinated solvent (e.g., 1,3-bis(trifluoromethyl)benzene) for a period of time.
[0062] According to certain embodiments, the polymer is immersed in the solvent capable of dissolving the uncrosslinked polymer for a period of time that is 5 seconds or more, 6 seconds or more, 7 seconds or more, 8 seconds or more, 9 seconds or more, 10 seconds or more, 15 seconds or more, 20 seconds or more, 30 seconds or more, 45 seconds or more, 60 seconds or more, 90 seconds or more.
[0063] In order to measure the specific electrochemical impedance modulus of the polymer after immersion in a solvent capable of dissolving the uncrosslinked polymer, the polymer is first dried according to certain embodiments. Drying of the polymer may be performed by any suitable method. For example, the polymer may be dried in nitrogen, air, or vacuum.
[0064] Combinations of impedance frequency measurements, specific electrochemical impedance modulus reduction and / or specific electrochemical impedance modulus values, polymer thickness, polymer immersion time, drying method, and solvents capable of dissolving the polymer when not crosslinked are also possible. For example, according to certain embodiments, a polymer is formed into an article having a minimum dimension of at least 0.3 micrometers that is immersed in 1,3-bis(trifluoromethyl)benzene for a time of 9 seconds or more, dried in nitrogen, and has a minimum dimension of at least 10 micrometers when measured at 1 kHz. 6 As another example, according to certain embodiments, a polymer may be formed into an article having a minimum dimension of at least 0.3 micrometers and a minimum dimension of no more than 3.0 micrometers, immersed in 1,3-bis(trifluoromethyl)benzene for 30 seconds or more, dried in nitrogen, and exhibits a specific electrochemical impedance modulus of at least 10 when measured at 1 kHz. 6 The specific electrochemical impedance modulus in Ω·m is shown.
[0065] In some embodiments, the polymer has a molecular weight (e.g., weight average molecular weight) before crosslinking that is 1000 kDa or less, 500 kDa or less, 200 kDa or less, 100 kDa or less, 50 kDa or less, 40 kDa or less, 30 kDa or less, 20 kDa or less, 15 kDa or less, 10 kDa or less, 8 kDa or less, 5 kDa or less, or less than 5 kDa, according to certain embodiments. The weight average molecular weight of the polymer according to certain embodiments is 1 kDa or more, 2 kDa or more, 3 kDa or more, 4 kDa or more, 5 kDa or more, 8 kDa or more, 10 kDa or more, 15 kDa or more, 20 kDa or more, 30 kDa or more, 40 kDa or more, or more than 40 kDa. Combinations of these ranges are also possible. For example, according to certain embodiments, the weight average molecular weight of the polymer may be 1 kDa or more and 8 kDa or less. According to other embodiments, the weight average molecular weight of the polymer may be greater than or equal to 20 kDa. The weight average molecular weight of the polymer may be determined by any suitable method, for example, gel permeation chromatography.
[0066] According to certain embodiments, the polymer may be an elastomer. For example, in some embodiments, the polymer may exhibit a low elastic modulus. For example, according to certain embodiments, the polymer has an elastic modulus of less than 10 MPa, less than 5 MPa, less than 2 MPa, less than 1 MPa, or less than 1 MPa. In some embodiments, the polymer may exhibit a high elastic tensile deformation. For example, in some embodiments, the polymer may exhibit an elastic tensile deformation at 20% strain, 30% strain, 50% strain, or 100% strain or more. In some embodiments, a combination of these mechanical properties is possible. For example, in some embodiments, the polymer may have an elastic modulus of less than 1 MPa and exhibit an elastic tensile deformation at 20% strain or more. The elastic modulus and / or elastic tensile deformation may be determined by any suitable method. For example, the elastic modulus and elastic tensile deformation may be measured using a tensile tester.
[0067] Some aspects are directed to methods of preparing an article comprising a fluorinated polymer. In some embodiments, the fluorinated polymer is deposited on a substrate. Some aspects are directed to methods for preparing an article comprising a perfluoropolymer. In some embodiments, the perfluoropolymer (e.g., perfluoropolyether) is deposited on a substrate. The substrate may provide mechanical support to the article, according to certain embodiments. In some embodiments, the substrate may functionally interact with the article, for example, when the article overlaps a portion of the circuitry of the substrate.
[0068] The substrate may comprise any suitable material. For example, the substrate may be a semiconductor substrate. The semiconductor may comprise any suitable material. According to certain embodiments, the substrate may comprise silicon, germanium, gallium arsenide, or combinations thereof. Other substrates are possible, for example substrates comprising semiconductors.
[0069] In certain embodiments, the substrate is coated. In some embodiments, the coating of the substrate can function as a release layer. A release layer is a layer that can facilitate separation of the article from the substrate, for example, through its degradation. In some embodiments, a spacer is added to the substrate. The spacer can include, for example, a photoresist. According to certain embodiments, the addition of a spacer to the substrate can advantageously protect the article. For example, according to certain embodiments, the spacer of the substrate is used to protect the article from contact with a mask (e.g., a photoaligner mask) or from contact with a nitrogen diffuser.
[0070] For example, in some embodiments, the substrate is coated with a photoresist. Examples of photoresists include epoxy-based photoresists, such as a mixture of bisphenol A novolac epoxy and triarylsulfinium / hexafluoroantimonate salt (SU-8 photoresist), and a mixture of diazonaptoquinone (DNQ) and phenol formaldehyde resin (DNQ-novolac). In certain embodiments, the substrate is coated with a metal (e.g., nickel).
[0071] The polymer may be treated with a plasma. For example, in some embodiments, the plasma is applied to the fluorinated polymer to form a treated fluorinated polymer. In some embodiments, the plasma is applied to the perfluoropolymer to form a treated perfluoropolymer. Any suitable plasma may be used. According to certain embodiments, the plasma is or includes an atomic forming inert gas. For example, according to certain embodiments, the plasma includes nitrogen. According to certain embodiments, the plasma includes argon. The treatment of the fluorinated polymer may advantageously prepare the surface of the fluorinated polymer for interaction with an external material. For example, the treatment of the fluorinated polymer may, according to certain embodiments, introduce reactive, charged, and / or polarized sites on the surface of the fluorinated polymer, which may form chemical or physical bonds with a subsequently deposited material. In some embodiments, the treatment of the perfluoropolymer advantageously prepares the surface of the perfluoropolymer for interaction with an external material. For example, the treatment of the perfluoropolymer may, according to certain embodiments, introduce reactive, charged, and / or polarized sites on the surface of the perfluoropolymer, which may form chemical or physical bonds with a subsequently deposited material.
[0072] Treatment of perfluoropolymers with a plasma formed from an inert gas can advantageously exclude oxygen from the treated perfluoropolymer in some embodiments. This can prevent oxygen from reacting with the treated surface and advantageously improve the ability of the perfluoropolymer to adhere to other materials. More generally, fluorinated polymers can be treated in some embodiments in a manner that advantageously excludes oxygen from the treated fluorinated polymer. This can prevent oxygen from reacting with the treated surface and advantageously improve the ability of the fluorinated polymer to bond to other materials. As a result, in certain embodiments, arbitrarily thick and / or multi-layered articles comprising perfluoropolymers can be made. Similarly, arbitrarily thick and / or multi-layered articles comprising fluorinated polymers can be made in certain embodiments. Making multi-layered articles comprising fluorinated polymers can provide substantial advantages in the preparation of articles comprising high number density electrodes. For example, as described in more detail elsewhere herein, making additional rows of electrodes on a sensor can include making additional layers of the device.
[0073] After the formation of the treated fluorinated polymer, an additional material can be deposited on the treated fluorinated polymer. In some embodiments, after the formation of the treated perfluoropolymer (e.g., perfluoropolyether), an additional material is deposited on the treated perfluoropolymer. The deposited additional material can be a conductive material or other material. For example, in some embodiments, the deposited additional material can include a metal or metal alloy. According to certain embodiments, the ability to deposit a conductive material is advantageous because it can be used to create part of an electronic circuit (e.g., a sensor). For example, the conductive material can be used to create an electrode.
[0074] In some embodiments, the additional material is a polymer. In certain embodiments, the polymer is not a perfluoropolymer. In certain embodiments, the additional material is not a fluorinated polymer. In certain embodiments, the additional material is a photoresist.
[0075] According to certain embodiments, the polymer can be deposited on the perfluoropolymer processed by solution processing. More generally, the polymer can be deposited on the fluorinated polymer processed via solution processing. Due to the hydrophobicity of the perfluoropolymer, according to some embodiments, the perfluoropolymer does not swell in the presence of non-fluorinated solvents. Similarly, in some embodiments, the fluorinated polymer may not swell in the presence of non-fluorinated solvents due to its hydrophobicity. The fluorinated polymer may experience low volumetric swelling during solution processing of the additive material. The perfluoropolymer may experience volumetric swelling of 5% or less, 2% or less, 1% or less, 0.5% or less, 0.2% or less, or less, in some embodiments. For example, the perfluoropolymer may experience volumetric swelling of 5% or less, 2% or less, 1% or less, 0.5% or less, 0.2% or less, or less. According to certain embodiments, the low volumetric swelling of the perfluoropolymer advantageously allows for the retention of patterns with high lateral resolution, including multiple layers of chemically distinct polymers. More generally, fluorinated polymers advantageously have low volume swelling, and as a result are capable of supporting patterns with high lateral resolution, including multiple layers of chemically distinct polymers.
[0076] The deposited additional material may be an additional fluorinated polymer (e.g., an additional layer of fluorinated polymer). This may result in a thicker layer of fluorinated polymer. In some embodiments, the fluorinated polymer layer has a minimum dimension of at least 0.3 micrometers, at least 0.5 micrometers, at least 0.7 micrometers, or more, indicating a high degree of crosslinking. In some embodiments, the fluorinated polymer layer has a minimum dimension of 3 micrometers or less, 2.5 micrometers or less, 2 micrometers or less, or 1 micrometer or less. Combinations of these ranges are also possible. For example, according to certain embodiments, the fluorinated polymer layer has a minimum dimension of at least 0.3 micrometers or more and 3 micrometers or less.
[0077] In some embodiments, the deposited additional material is an additional layer of perfluoropolymer. In certain embodiments, depositing an additional layer of perfluoropolymer can result in a thicker layer of perfluoropolymer. In some embodiments, the perfluoropolymer layer has a minimum dimension of at least 0.3 μm, at least 0.5 μm, at least 0.7 μm, or more, indicating a high degree of crosslinking. In some embodiments, the perfluoropolymer layer has a minimum dimension of 3 micrometers or less, 2.5 micrometers or less, 2 micrometers or less, or 1 micrometer or less. Combinations of these ranges are also possible. For example, according to certain embodiments, the perfluoropolymer layer has a minimum dimension of at least 0.3 micrometers or more and 3 micrometers or less.
[0078] 3 shows an exemplary representation of the method. First, a perfluoropolymer 204 is deposited on a substrate 200 including a semiconductor 201 coated with a release layer 202. Next, a plasma is applied to the perfluoropolymer 204 to form a treated perfluoropolymer 206. After formation of the treated perfluoropolymer layer 204a, a material 208 is deposited on the treated perfluoropolymer layer 204a. Of course, it should be understood that the same method can be performed with any of a variety of fluorinated polymers as described above and is not limited to perfluoropolymers in particular.
[0079] In addition, certain aspects of the disclosure are directed to articles formed from the methods as described herein. According to one aspect, for example, the article may include one or more layers, for example, formed as described above. For example, in some embodiments, the article includes a first layer, a second layer, and a third layer. According to certain embodiments, the first layer includes a polymer. The first layer may include a fluorinated polymer. For example, the first layer may include a perfluoropolymer (e.g., perfluoropolyether). In some embodiments, the second layer is bonded to the first layer. In some embodiments, the third layer is bonded to the second layer. The third layer may include a fluorinated polymer. The layers that are bonded may be directly bonded or may be separated by one or more intervening layers that connect them.
[0080] In one aspect, the present disclosure is directed to an article comprising a perfluoropolymer (e.g., perfluoropolyether). In some embodiments, the article comprises a first layer comprising a perfluoropolymer (e.g., perfluoropolyether). According to certain embodiments, the article comprises a second layer bonded to the first layer. In some embodiments, the article comprises a third layer bonded to the second layer and comprising a perfluoropolymer (e.g., perfluoropolyether). According to certain embodiments, the article comprises one or more additional layers (e.g., above the third layer). These may be formed, for example, as discussed herein.
[0081] In another aspect, the present disclosure is directed to an article comprising a fluorinated polymer. In some embodiments, the article comprises a first layer comprising a fluorinated polymer. According to certain embodiments, the article comprises a second layer bonded to the first layer. In some embodiments, the article comprises a third layer bonded to the second layer and comprising a fluorinated polymer. According to certain embodiments, the article comprises one or more additional layers (e.g., above the third layer). These may be formed, for example, as discussed herein.
[0082] Some embodiments can further include one or more additional layers. For example, embodiments can include additional layers to promote bonding between the first, second, and / or third layers; a layer to modify the dielectric properties of the article; a sensing layer; and / or a layer to insulate the article (e.g., electrically insulating, thermally insulating, chemically insulating, etc.). The one or more additional layers can include an intervening layer, such as a layer between the first layer and the second layer, and / or can be an external layer, such as a layer deposited on the third layer.
[0083] According to certain embodiments, the first layer has a thickness of 50 nanometers or more, 100 nanometers or more, 200 nanometers or more, 300 nanometers or more, 400 nanometers or more, 500 nanometers or more. According to certain embodiments, the first layer has a thickness of 5000 nanometers or less, 4000 nanometers or less, 3000 nanometers or less, 2000 nanometers or less, 1000 nanometers or less, 500 nanometers or less. Combinations of these ranges are also possible. For example, according to some embodiments, the first layer has a thickness of 50 nanometers or more and 5000 nanometers or less. As another example, according to some embodiments, the first layer has a thickness of 300 nanometers or more and 2000 nanometers or less.
[0084] According to certain embodiments, the second layer has a thickness of 50 nanometers or more, 100 nanometers or more, 200 nanometers or more, 300 nanometers or more, 400 nanometers or more, 500 nanometers or more. According to certain embodiments, the second layer has a thickness of 5000 nanometers or less, 4000 nanometers or less, 3000 nanometers or less, 2000 nanometers or less, 1000 nanometers or less, 500 nanometers or less. Combinations of these ranges are also possible. For example, according to some embodiments, the second layer has a thickness of 50 nanometers or more and 5000 nanometers or less. As another example, according to some embodiments, the second layer has a thickness of 300 nanometers or more and 2000 nanometers or less.
[0085] According to certain embodiments, the third layer has a thickness of 50 nanometers or more, 100 nanometers or more, 200 nanometers or more, 300 nanometers or more, 400 nanometers or more, 500 nanometers or more. According to certain embodiments, the third layer has a thickness of 5000 nanometers or less, 4000 nanometers or less, 3000 nanometers or less, 2000 nanometers or less, 1000 nanometers or less, 500 nanometers or less. Combinations of these ranges are also possible. For example, according to some embodiments, the third layer has a thickness of 50 nanometers or more and 5000 nanometers or less. As another example, according to some embodiments, the third layer has a thickness of 300 nanometers or more and 2000 nanometers or less.
[0086] According to certain embodiments, the second layer overlaps 5% or more, 10% or more, 25% or more, 50% or more, 75% or more, 90% or more, 95% or more, 99% or more, or more of the surface area of the first layer. According to certain embodiments, the second layer overlaps 100% or less, 95% or less, 90% or less, 75% or less, 50% or less, 25% or less, or less, of the surface area of the first layer. Combinations of these ranges are possible. For example, according to certain embodiments, the second layer overlaps 5% or more and 100% or less of the surface area of the first layer.
[0087] According to certain embodiments, the second layer overlaps 5% or more, 10% or more, 25% or more, 50% or more, 75% or more, 90% or more, 95% or more, 99% or more, or more of the surface area of the third layer. According to certain embodiments, the second layer overlaps 100% or less, 95% or less, 90% or less, 75% or less, 50% or less, 25% or less, or less, of the surface area of the third layer. Combinations of these ranges are possible. For example, according to certain embodiments, the second layer overlaps 5% or more and 100% or less of the surface area of the third layer.
[0088] In some embodiments, two layers are considered to overlap in a region if a ray of light perpendicular to the surface of one layer and directed away from one layer extends through the other layer. Overlapping layers need not be in direct contact with each other. They may be in direct contact with each other or may be separated (e.g., by one or more intervening layers). Additionally, in various embodiments, one or more (or all) of the layers may be substantially planar and / or rectangular, although it should be understood that this is not necessarily a requirement.
[0089] According to certain embodiments, a portion of the second layer does not overlap with the first layer and / or the third layer. For example, according to certain embodiments, a portion of the second layer is exposed (e.g., to form an electrode). According to some embodiments, a portion of the second layer is covered by a non-fluorinated polymer. For example, according to certain embodiments, a portion of the second layer (e.g., an electrode) may be covered by a layer of a conductive polymer (e.g., PEDOT:PSS).
[0090] The articles described herein may include at least three layers, but in some embodiments, the articles described herein may include one or more layers. For example, the articles described herein may include 1, 2, 3, 4, 5, 8, 10, 15, 20, 25, or more layers. In some embodiments, the articles described herein may include 100 or less, 50 or less, 25 or less, or fewer articles. Combinations of these ranges are also possible. For example, the articles described herein may include 1 or more layers and 100 or less layers. In some embodiments, the articles include multiple polymer layers (e.g., fluorinated polymer layers). As an example, the articles may include alternating conductive layers and polymer layers.
[0091] In some embodiments, the article includes a conductive layer adjacent to a plurality of layers of the article (e.g., adjacent to a fluorinated polymer layer of the article). For example, in some embodiments, the article includes an electrode. The electrode may be a surface electrode of the article. The article may include a plurality of electrodes (e.g., a plurality of surface electrodes). In some embodiments, the article includes a substrate (e.g., a substrate designed to be implanted in a subject). The substrate may include a plurality of electrodes. According to some embodiments, the electrode may be formed on the article by depositing a material on the treated fluorinated polymer of the article, as described above. For example, the electrode may be formed by depositing a metal layer on the treated fluorinated polymer layer, as described above. In some embodiments, the electrode may be electrically connected to the conductive layer of the article. For example, the electrode may be in contact with a metal layer of the article such that the electrode may be electrically connected to an external circuit.
[0092] The article may be used to determine electrical activity using multiple electrodes on a substrate of the article that is at least partially contained within a subject. In some embodiments, electrodes may be used to determine electrical activity. For example, multiple electrodes may be used to determine electrical activity. The electrical activity may be neural activity. For example, the electrodes may be used to determine electrical activity of a single cell within a subject (e.g., a living subject). For example, the cell may be a neural cell. The electrodes may be in contact with the cell for a period of time. For example, in some embodiments, the electrodes are in contact with the cell for a period of 1 day or more, 5 days or more, 7 days or more, 14 days or more, 3 weeks or more, 4 weeks or more, or more. In some embodiments, the electrodes are in contact with the cell for a period of 6 months or less, 3 months or less, 6 weeks or less, 5 weeks or less, 4 weeks or less, 14 days or less, or less. Combinations of these ranges are also possible. For example, in some embodiments, the electrodes are in contact with the cell for a period of 1 day or more and 6 months or less. In some embodiments, the electrodes are in contact with the cell continuously for a period of time (e.g., at least 5 days). In some embodiments, the electrodes are adapted to intermittently monitor electrical activity from near the cells over a period of time.
[0093] In certain embodiments, the electrodes may be used to electrically stimulate cells. For example, multiple electrodes may be used to stimulate cells. The electrodes may be used to stimulate neural activity. For example, the electrodes may be used to stimulate electrical activity of neurons in a subject (e.g., a living subject). In some embodiments, the electrodes may be used to stimulate neurons in the vicinity of a brain probe.
[0094] The article may include electrodes having an electrode number density. The electrode number density may be the area density of the electrodes located on the implant portion of the article (e.g., the substrate of the article). In some embodiments, the electrodes are 10 -5 Electrode / micron 2 That's it, 10 -4 Electrode / micron2 That's it, 10 -3 Electrode / micron 2 That's it, 10 -2 Electrode / micron 2 That's it, 10 -1 Electrode / micron 2 In some embodiments, the electrodes have an electrode number density of 10 1 Electrode / micron 2 Below, 10 0 Electrode / micron 2 Below, 10 -1 Electrode / micron 2 Combinations of these ranges are also possible. For example, in some embodiments, the electrodes have an electrode number density of 10 -5 Electrode / micron 2 That's it, 10 1 Electrode / micron 2 The electrode number density is as follows:
[0095] In some embodiments, the article may be patterned (e.g., by a mask), as described in more detail below. The article may have a resolution (e.g., spatial resolution). In some cases, the resolution may be determined as a lateral resolution. One advantage of certain articles described herein is that they have a high lateral resolution. For example, in some embodiments, the article has a lateral resolution of 30 micrometers or less, 20 micrometers or less, 10 micrometers or less, 5 micrometers or less, 2 micrometers or less, or less. The lateral resolution of the structure may be determined by any suitable technique, such as scanning electron microscopy.
[0096] In some embodiments, the article is on a substrate (e.g., a semiconductor substrate). In some embodiments, the article is not on the substrate, e.g., because it is separated from the substrate. According to certain embodiments, the substrate includes (e.g., is coated with) a release layer, as described above. In some embodiments, providing the article on a substrate that includes a release layer may facilitate separation of the article from the photoresist.
[0097] Perfluoropolyether can have any suitable molecular weight. According to certain embodiments, perfluoropolymer (e.g., perfluoropolyether) can be advantageously of low molecular weight (e.g., weight average molecular weight less than 8 kDa, or other molecular weight as described herein). In some embodiments, the low molecular weight of perfluoropolymer ensures that perfluoropolyether maintains rigidity when crosslinked to substrate, resulting in rigid perfluoropolyether.
[0098] According to certain embodiments, it may be advantageous for the perfluorinated polymer to have a high molecular weight (e.g., weight average molecular weight of 20 kDa or more). According to certain embodiments, the high molecular weight of the perfluorinated polymer may provide the perfluorinated polymer with advantageous physical properties for sensing applications. For example, according to certain embodiments, the high molecular weight of the perfluorinated polymer may mean that the perfluorinated polymer is an elastomer.
[0099] In some embodiments, the second layer comprises a conductive material. This may be advantageous in certain embodiments, for example, if the article is part of a device such as described below, since it allows the article to be electronically connected to the device. This may also allow the article to function as a sensor of such a device, according to certain embodiments, since an electrical signal received by a part of the article can be conducted through the article to the device. In some embodiments, the second layer comprises a metal or metal alloy, such as aluminum, silver, copper, gold, etc. The second layer may be deposited by any suitable method. For example, the second layer may be deposited by vapor deposition (e.g., physical vapor deposition, chemical vapor deposition). According to certain embodiments, the second layer may be electronically connected to an electrode (e.g., a working electrode).
[0100] The articles described herein can have suitable mechanical properties. For example, in some embodiments, the electrodes can be 10 3 Pa or above, 10 4 Pa or above, 105 Pa or above, 10 6 In some embodiments, the electrode has a total modulus of elasticity of 10 Pa or more. 9 Pa or less, 10 8 Pa or less, 10 7 Pa or less, 10 6 A combination of these ranges is also possible. For example, in some embodiments, the electrode has a total modulus of 10 3 Pa or more 10 9 It has a total modulus of elasticity of less than 1 Pa.
[0101] In some embodiments, the article comprises 10 -11 Electrode / micron 2 -Pa or above, 10 -10 Electrode / micron 2 -Pa or above, 10 -9 Electrode / micron 2 -Pa or above, 10 -8 Electrode / micron 2 In some embodiments, the article comprises a substrate having a ratio of electrode number density to total modulus of elasticity of 10 -Pa or greater. -6 Electrode / micron 2 -Pa or less, 10 -7 Electrode / micron 2 -Pa or less, 10 -8 Electrode / micron 2 -Pa or less, 10 -9 Electrode / micron 2 -Pa or less, or a ratio of electrode number density to total modulus of elasticity of less than 10 -11 Electrode / micron 2 -Pa or above, 10 -6 Electrode / micron 2 The substrate has a ratio of electrode number density to total modulus of elasticity of less than 0.1 Pa.
[0102] Another aspect of the present disclosure is directed to various devices. In certain embodiments, these devices may be exposed to physiological conditions. For example, in some embodiments, these devices may be implanted in a subject. According to certain embodiments, the device includes an electronic circuit. In some embodiments, the article covers at least a portion of the electronic circuit of the device. For example, according to some embodiments, electrodes of the article cover electrodes of the electronic circuit. According to certain embodiments, the article and the electronic circuit are in electronic communication. In some cases, the electronic circuit may be adapted to receive a signal (e.g., an electronic signal) from the article. In some cases, the electronic circuit may be adapted to, for example, amplify a signal from the article, and according to certain embodiments, the article may be used as a sensor (e.g., a sensor of neural activity).
[0103] In certain embodiments, the method includes applying light to the substrate. For example, according to certain embodiments, the light can be applied to a substrate including a photoresist. According to certain embodiments, the light is applied through a mask. In some cases, the mask defines a pattern. For example, in some embodiments, the mask defines a pattern of light on the substrate. The method can include aligning and patterning a fluorinated polymer (e.g., a perfluoropolymer). The method can include aligning and patterning a perfluoropolyether, according to certain embodiments. The fluorinated polymer can be aligned with respect to the mask. For example, according to certain embodiments, the perfluoropolyether is aligned with respect to the mask (e.g., a photoaligner mask). According to certain embodiments, the alignment includes moving the mask relative to the substrate. In some embodiments, photoresist spacers are deposited on the substrate including the polymer, as described above. According to certain embodiments, the addition of the spacers allows the mask to contact the spacers without contacting the polymer. Advantageously, according to certain embodiments, the addition of spacers can prevent the mask from damaging the polymer during alignment. In some embodiments, material is deposited on the substrate and / or photoresist based on the pattern of the mask. For example, the material may be a metal. In some embodiments, portions of the photoresist are removed to produce a substrate patterned with the deposited material.
[0104] In certain embodiments, the pattern has a lateral resolution, for example, in some embodiments, the pattern has a lateral resolution of 30 micrometers or less, 20 micrometers or less, 10 micrometers or less, 5 micrometers or less, 2 micrometers or less, or less.
[0105] According to certain embodiments, the light has an average wavelength. In some embodiments, the average wavelength of the light is 1500 nanometers or less, 1000 nanometers or less, 800 nanometers or less, 750 nanometers or less, or 600 nanometers or less. In some embodiments, the average wavelength of the light is 100 nanometers or more, 200 nanometers or more, 300 nanometers or more, or more. Combinations of these ranges are possible. For example, according to some embodiments, the average wavelength of the light is 100 nanometers or more and 1500 nanometers or less.
[0106] In some embodiments, at least a portion of the article (e.g., sensor, substrate, etc.) is implanted in the subject. For example, the article may be partially or entirely implanted in the subject. The article may be implanted at a location in the subject. For example, the article may be implanted in the brain. In some embodiments, the article is intended for long-term internal placement in the subject. For example, the article may be intended for long-term internal placement in an organ of the subject. For example, the article may become long-term internally resident in the brain of the subject. In some embodiments, the article may be a brain probe or a neurosensor.
[0107] The following applications are each incorporated by reference in their entirety for all purposes: U.S. Provisional Application No. 63 / 159,623, filed March 11, 2021, entitled "Perfluorinated Elastomers for Brain Probes and Other Applications," and U.S. Provisional Application No. 63 / 290,732, filed December 17, 2021, entitled "Fluorinated Elastomers for Brain Probes and Other Applications."
[0108] The following examples are intended to illustrate certain embodiments of the present invention, but do not exemplify the full scope of the invention.
[0109] Example 1 This example describes a method for fabricating metal interconnects on the surface of a perfluoropolyether layer. In this example, the perfluoropolyether is perfluoropolyether dimethyl acrylate (PFPE-DMA), an elastomer. First, a layer of PFPE-DMA was fabricated on a substrate. Next, photoresist was deposited on the PFPE-DMA layer. Using a nitrogen chamber and a mask aligner, the photoresist was photolyzed to pattern the surface, exposing the patterned portions of the PFPE-DMA layer. The lateral resolution of the patterned portions of the PFPE-DMA was less than 5 micrometers. The patterned portions of the PFPE-DMA were exposed to an argon plasma to form a treated PFPE-DMA, and an aluminum tie layer was sputtered onto the exposed surface. Next, gold was evaporated onto the aluminum to form a gold interconnect and electrode layer on the patterned portions of the PFPE-DMA layer. Finally, the excess metal was removed by a lift-off process. In this example, the remaining photoresist was photolyzed to remove the excess metal deposited on the photoresist. As a result, patterned gold circuitry, including gold interconnects and electrodes, was deposited on the surface of the PFPE-DMA layer with a lateral resolution of less than 5 micrometers.
[0110] In some cases, a second argon plasma exposure was performed without a mask to allow for the deposition of additional layers. For example, in one case, a PFPE-DMA layer was deposited on top of the circuitry to form a third layer that encapsulates the conductive layer. In some cases, a first argon plasma exposure was performed without a mask to deposit a PFPE-DMA layer on top of a previously deposited PFPE-DMA layer. By repeating this process, it was possible to create PFPE-DMA layers with thicknesses of over 300 nanometers. As a result, electronics could be fabricated on PFPE-DMA layers with thicknesses of over 300 nanometers. By repeating this approach, it may be possible to create multilayer encapsulated circuits within the PFPE-DMA layer.
[0111] These results demonstrate the fabrication of multilayer articles containing a perfluoropolyether layer. In particular, these results demonstrate that such multilayer articles can be used to fabricate circuits containing gold electrodes and gold interconnects encapsulated within the PFPE-DMA.
[0112] Example 2 In some cases, deposited perfluoropolyether layers can exhibit high specific electrochemical impedance modulus after extended exposure to aqueous salt solutions. In this example, we compare the measured decrease in specific electrochemical impedance modulus of polymers after extended immersion in 1x or 10x phosphate buffer solutions at 37°C or 70°C. Layers of perfluoropolyethers such as PFPE-DMA were compared to layers of polydimethylsiloxane (PDMS), styrene-ethylene-butylene-styrene (H-SEBS), polyimide (PI), and SU-8 2000.5 epoxy photoresist.
[0113] Electrochemical impedance measurements were performed in phosphate buffer using a standard three-electrode setup for measuring electrochemical impedance. Figure 2 shows the setup for three-electrode electrochemical impedance measurements. In these experiments, a working electrode (gold) 122 was connected to a conductor 108 deposited on a substrate 124 and encapsulated within a dielectric layer 126 containing one of the polymers. Two electrodes, a counter electrode 110 (platinum) and a reference electrode 112 (silver / silver chloride), were connected to the other side of the dielectric layer and electrochemical impedance was measured using a Bio-logic (copyright) SP-150 potentiostat and commercially available software (EC-lab). The experiments were performed in a buffer solution 114. With this technique, the ionic diffusivity can be estimated from the time required to observe a drop in impedance, and the ionic conductivity can be estimated from the resulting Nyquist plot.
[0114] For each measurement, the frequency was swept three times from 1 MHz to 0.1 Hz. A sinusoidal voltage of 100 mV peak-to-peak was applied. Five points were measured per frequency decade, logarithmically spaced. For each data point, the response to 10 consecutive sinusoids (but spaced 10% of the period) was accumulated and averaged. The thickness H of each layer was determined as a fraction of a micrometer (e.g., a 3-micrometer-thick sample is represented by H=3.0). All thickness measurements were made with a Bruker Dektak Xt stylus profiler. The applied force was set at 1 milligram, and the scan speed was set at 0.67 micrometers per second. Two-point surface leveling (m or surface leveling) was performed using commercially available software.
[0115] The polymer layers were immersed in 10 times (or 10x) phosphate buffer solution (PBS) under rapid aging conditions at 70 °C. Figure 4A plots the specific electrochemical impedance modulus (top) and phase (bottom) of the dielectric polymers under initial conditions and after aging in 10x PBS at 70 °C (t / H for PFPE, SU-8, H-SEBS, and PI). 2 = 5 days / micrometer 2 , t / H for PDMS 2 = 1.55 days / micrometer 2 4B and 4C show the electrochemical impedance modulus of the immersed layer as a function of time, measured at 1 kHz and 1 Hz, respectively (H 2(normalized by ). Under rapid aging conditions, the specific electrochemical impedance modulus decreased for all polymers. However, the specific electrochemical impedance modulus of the PFPE-DMA layer, as well as that of the SU-8 layer, decreased very slowly compared to the specific electrochemical impedance modulus of the other polymers. These data demonstrate the long-term stability of the perfluoropolyether layer under physiological salt conditions. Figure 4D is similar to Figure 4B, but with the addition of specific electrochemical impedance measurements recorded for the PFPE-DMA layer under physiological conditions (37 °C, 1x PBS). This visualization shows the stability of the PFPE-DMA layer over more than 250 days under physiological conditions.
[0116] These results were further verified by conductance measurements. For these measurements, large-area (150–300 cm2) films were prepared on glass slides following the protocol used for film preparation for electrochemical impedance measurements. 2 ) dielectric thin film was prepared and immersed in deionized water to facilitate peeling. After peeling, the crumpled thin film was transferred to a glass vial and used for the remaining experiments. To remove impurities that contribute to ionic conductivity, the crumpled thin film was first immersed in periodically replaced deionized water at room temperature for three weeks. A conductivity meter (Traceable® Conductivity Pocket Tester with Calibration) was used to confirm that the conductivity of the surrounding solution remained negligible after three weeks, confirming that the cleaning process was complete. The area of the two electrodes of the conductivity meter was 1 cm. 2 The sensor resolution was 1 microsiemens, and the temperature dependence of the conductance in the range -5 to 50 °C was automatically corrected to give the value at 25 °C.
[0117] The samples were transferred to new glass vials with a large volume of 10x PBS solution to allow for complete immersion of the ions at constant temperature (4°C, 37°C or 65°C) for 3 weeks. It was verified a posteriori that 3 weeks is a long time compared to the characteristic diffusion time of ions in the material. After the immersion in the biofluid reached equilibrium, the samples were thoroughly rinsed twice in succession with deionized water (30 s each) to remove ions attached to the surface, and then dried at 65°C for 30 min before mass measurements were taken.
[0118] The samples were then transferred to new glass vials containing 4.00 mL of deionized water and stored at a constant temperature (4 °C, 37 °C or 65 °C). The water contained a conductivity measurement cell to monitor temperature and conductance. The conductance of the deionized water solutions was measured periodically to determine the amount of ions desorbed by each material over time. This process is shown diagrammatically in Figure 5A, where the perfluoropolyether is shown in the presence of a conductance meter to absorb ions as it equilibrates in deionized (DI) water, then in 10x phosphate buffer, then releases ions as it equilibrates again in DI water. Figure 5B shows the boundary conditions and diffusion profiles resulting from such conditions, showing the change in concentration profile at different times. The change in conductance allowed us to determine the concentration of ions desorbed by each dielectric polymer over time, at various temperatures. Figure 5C shows the results of these experiments, showing the ion concentration in the initial deionized water for each polymer as a function of time at 4 °C, 37 °C and 65 °C (H 2 normalized by .
[0119] The concentration plateau is directly proportional to the ionic solubility S of the polymer, and the corresponding theoretical solution of the diffusion one-dimensional boundary problem was fitted to the experimental data to determine the ionic diffusivity D. Figure 5D shows the experimental results and theoretical fits for each polymer at 37°C. The ionic conductivity was then calculated using equation (1) and is shown in Figure 6. Equation 1
[0120] TIFF2024512401000002.tif1795Here, σ (sigma) is ionic conductivity, q is unit charge, k is Boltzmann constant, T is temperature, D is ionic diffusivity, S is ionic solubility, C out is the ion concentration in the surrounding biofluid at equilibrium. In Figure 5E, the ionic conductivity determined by electrochemical impedance measurements (Method #1) is compared to that determined by conductance measurements (Method #2) and shows good agreement. Both measurements agreed in both general trend and order of magnitude. According to both measurements, PFPE-DMA has lower ionic conductivity compared to other dielectric elastomers, which is due to its lower ionic diffusivity (Table 2).
[0121] [Table 1]
[0122] To further understand the nature of the low ionic conductivity in PFPE-DMA, conductance was measured at various temperatures and the Arrhenius relationship was used to determine the average activation energy of diffusion and heat of solution of the ions in the range of 4 °C to 65 °C. Figures 7A-7C are Arrhenius plots of the ion diffusivity D (Figure 7A), ion solubility S (Figure 7B), and ion permeability P (Figure 7C) measured for each polymer. A linear fit was used to obtain the energy parameters in Table 2. In both diffusivity and solubility trends, PFPE-DMA is closer to SU-8 than the other elastomers.
[0123] [Table 2]
[0124] Example 3 This example shows how to characterize the crosslinking of a perfluoropolyether layer using specific electrochemical impedance measurements. To do this, a deposited layer of perfluoropolyether, in this case PFPE-DMA, of thickness H (as described in Example 2) is heated for 30 s / H with gentle agitation to remove uncrosslinked polymer chains. 2 The films were then immersed in 1,3-bis(trifluoromethyl)benzene for a period of 10 min. The samples were then dried using a stream of nitrogen. Finally, the samples were immersed in 1× phosphate buffer and the electrochemical impedance was measured according to the protocol in Example 2. In general, films known to be highly crosslinked were observed to have substantially higher specific electrochemical impedance modulus, demonstrating that the specific electrochemical impedance modulus can be used as an indirect test of crosslinking in these films.
[0125] Example 4 This example describes the preparation of perfluoropolyether dimethyl acrylate (PFPE-DMA) photolithographic precursor. All chemicals were obtained from Sigma-Aldrich unless otherwise noted and were used without further purification. All volume fraction statements correspond to the volume of 1,1,1,3,3-pentafluorobutane.
[0126] First, 0.8 g / mL of PFPE diol was dissolved in 1,1,1,3,3-pentafluorobutane (Alfa Aesar, H33737). The solution was mixed for 3 hours. Then, 22 mg / mL of isophorone diisocyanate (IPDI, 317624), 0.8 mg / mL of dibutyltin diacetate (DBTDA, 290890) were added to the solution and reacted for 48 hours under nitrogen. The product was thick or solid. Next, 30 mg / mL 2-isocyanatoethyl methacrylate (IEM, 477060) and 0.8 mg / mL DBTDA were added to the product and reacted for another 48 hours at room temperature under nitrogen. The final product solution was filtered through a 0.2 micrometer glass fiber syringe filter to obtain a clear, colorless oil. The IPDI solvent in the oil was removed by rotary evaporation to obtain pure PFPE-DMA. Finally, 0.5-1.5 g / mL of PFPE-DMA and 1 wt% of the photopolymerization initiator bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (511447) were dissolved in bis(trifluoromethyl)benzene (251186) to obtain the precursor.
[0127] Example 5 This example shows an exemplary method used to make a particular article containing perfluoropolyether. In a more specific embodiment, this method was used to make a PFPE-DMA encapsulated brain probe. Figure 8 shows a schematic of this exemplary method. All photoresists and developers were obtained from MicroChem Corporation unless otherwise noted.
[0128] 1. The fabrication of the device began with the preparation of a Ni sacrificial layer (Figure 8, step 1). A 3-inch thermally oxidized silicon wafer (2005, University wafer) was rinsed with acetone, rinsed with isopropyl alcohol (IPA), rinsed with water and blown dry. The 3-inch thermally oxidized silicon wafer was then baked at 110 °C for 3 minutes and treated with an oxygen (O2) plasma at 100 W and 40 standard cubic centimeters per minute (sccm) for 30 seconds. Layers of hexamethyldisilazane, LOR 3A photoresist, and S1805 photoresist were spin-coated on the wafer at 4000 rpm for 1 minute. The LOR 3A photoresist was hard-baked at 180 °C for 5 minutes. After this, the S1805 photoresist was applied and hard-baked at 115 °C for 1 minute. The photoresist was then hard-baked at 40 mJ / cm2. 2 The wafer was exposed to UV light for 50 seconds and developed in CD26 developer for 50 seconds, then rinsed with pure water and blown dry. A 100-nanometer Ni layer was then thermally evaporated onto the wafer and stripped with Remover PG, an N-methyl-2-pyrrolidone (NMP)-based solvent stripper, for 3 hours.
[0129] 2. Next, spacers were fabricated using negative photoresist. SU-8 2010 epoxy photoresist was spin-coated onto the wafer at 3000 rpm for 2 min, pre-baked at 60 °C for 2 min, and then at 95 °C for 4 min. SU-8 2010 epoxy photoresist was applied at 200 mJ / cm 2 The resist was exposed to UV light for 200 s and post-baked at 60 °C for 2 min and 95 °C for 2 min 30 s. Finally, the SU-8 2010 epoxy photoresist was developed in SU-8 developer (1-methoxy-2-propanol acetate) for 2 min, rinsed with IPA, and then blow-dried.
[0130] 3. The bottom PFPE-DMA layer was fabricated (Figure 8, step 3). The wafer was first washed with acetone, IPA, water, and blow-dried. Next, the PFPE-DMA precursor described in Example 4 was spin-coated onto the wafer at a range of 2000-6000 rpm for 1 min and pre-baked at 95 °C for 1 min to obtain a thickness ranging from 500 nanometers to 3 micrometers depending on the spin speed and precursor concentration. The PFPE-DMA was aligned with a photomask aligner and then irradiated with 20 mJ / cm using an exemplary customized nitrogen diffuser. 2 The PFPE was patterned with UV. FIG. 9A shows a schematic of an exemplary nitrogen diffuser, and FIG. 9B shows a photograph of an exemplary nitrogen diffuser placed on a Karl Suss MA6 mask aligner. The PFPE was then post-baked at 95° C. for 1 min, developed with developer (bis(trifluoromethyl)benzene:1,1,1,3,3-pentafluorobutane=1:3) for 1 min, and blown dry. The PFPE pattern was hard-baked at 150° C. for 50 min.
[0131] 4. Metal traces were fabricated on the top surface of the bottom PFPE-DMA (Figure 8, step 4). The bottom PFPE was first surface-treated with argon plasma at 20–30 W and 40 sccm for 2–6 min.
[0132] 5. Positive photoresists LOR 3A and S1805 or S1813 were patterned on the wafer as described in step 1 to create a sacrificial layer. The surface was then treated again with argon plasma (20-30 W, 40 sccm argon, 2-6 min) and aluminum-gold, or aluminum-gold-aluminum, or aluminum-gold-platinum, or chromium-gold, or chromium-gold-chromium metal layers were deposited sequentially by sputtering with thicknesses ranging from 20 to 100 nanometers for each layer. Finally, the metal layers were stripped in remover PG overnight (Figure 8, step 5).
[0133] 6. The subsequent PFPE-DMA layer was deposited following the method described in step 3 (Figure 8, step 6).
[0134] 7. Steps 4 to 6 can be repeated multiple times to obtain the desired number of metal electrode layers, all fully encapsulated with perfluoroelastomer.
[0135] 8. Negative photoresist was used to create a microfabricated plastic frame that would hold the brain probe, encapsulated in perfluoroelastomer, flat during release. An alternative approach is to use SU-8 2010 spacers as described here (Figure 8, step 2). SU-8 2010 was spin-coated onto the wafer at 3000 rpm for 2 min, pre-baked at 60 °C for 2 min, then at 95 °C for 4 min. SU-8 was applied at 200 mJ / cm. 2 The film was exposed to UV light for 100 s and post-baked at 60 °C for 2 min and 95 °C for 2 min 30 s. Finally, the SU-8 2010 was developed in SU-8 developer for 2 min, rinsed with IPA and blow-dried. Depending on the final thickness of the microfabricated plastic frame, which must be thicker than the total thickness of the brain probe, different SU-8 can be used. This fabrication process was successfully applied with SU-8 2010, SU-8 2025 and SU-8 2050.
[0136] 9. In some embodiments, low electrochemical impedance materials were plated onto the electrode tips following a procedure similar to steps 4-5, replacing the metal with platinum, aluminum-platinum, or chromium-platinum, with thicknesses ranging from 20-80 nanometers. A Bio-logic (copyright) SP-150 potentiostat and commercially available software (EC-lab) were used for voltage or current control of electrodeposition. The electrodes of the device were connected to the working electrodes. The counter electrode was a platinum wire, immersed in the precursor solution, which also served as a voltage reference. For platinum black, the precursor was a 0.8 wt% chloroplatinic acid solution, and the applied current was -1 mA / cm. 2, for 5–10 min. For PEDOT-PSS deposition, an electrolyte consisting of 0.01 M 3,4-ethylenedioxythiophene (EDOT) (Sigma-Aldrich, USA) and 0.1 M sodium PSS (Sigma-Aldrich, USA) aqueous solution was used. The electrochemical polymerization reaction was carried out under constant voltage conditions. In the constant voltage mode, polymerization was carried out for 30 s at a constant current of 1 V.
[0137] Example 6 This example illustrates the properties of articles containing PFPE-DMA. To compare the electrochemical impedance stability of PFPE-DMA and SU-8, long-term immersion experiments were performed under physiological conditions (1x phosphate buffer at 37°C). The results of these electrochemical impedance measurements are shown in Figure 10A. Even after more than 15 months (more than 450 days), PFPE-DMA maintained a high specific electrochemical impedance modulus comparable to that of SU-8, sufficient to electrically insulate the brain probe. However, SU-8 is a stiff polymer with a modulus on the order of 2 gigapascals, whereas PFPE-DMA is an elastomer with a modulus of only 0.50 megapascals, according to certain embodiments, more than 4000 times softer. Stress-strain curves were determined using an Instron instrument in uniaxial tension on specimens in pure shear test geometry. Figure 10B shows the stress-strain curves for each polymer. FIG. 10C shows the relationship between the elastic modulus (E) and the specific electrochemical impedance at 1 kHz normalized modulus half-life (t 1 / 2 / H 2 ) (defined as the immersion time required to reduce the initial specific electrochemical impedance modulus by 50%), and the only material with a higher normalized half-life was the perfluoropolyether elastomer. 1 / 2 / H 2 A graphical representation of the determination is shown in FIG. 4B.
[0138] Example 7 This example demonstrates the nanofabrication of a brain probe containing a perfluoropolyether elastomer and demonstrates that PFPE-DMA does not swell and maintains nanometer-scale smoothness when immersed in organic solutions commonly used in photolithography.
[0139] PFPE-DMA was photopatterned using the exemplary customized nitrogen diffuser described in Example 4 to create an inert atmosphere during UV exposure and enable nanoscale photopatterning. To maintain the nanometer smoothness of the PFPE-DMA, negative photoresist spacers were patterned on the wafer to prevent direct contact of the uncrosslinked PFPE-DMA precursor with the photomask. Finally, the exposed surface of the PFPE-DMA was treated with an inert gas (N2, argon, etc.) plasma to promote bonding of metals and other evaporated materials to the PFPE-DMA.
[0140] An example of a device fabricated by this method is shown in Figure 11A. It has three layers of PFPE-DMA sandwiched between two layers of metal wiring. This fabrication workflow is amenable to wafer-scale fabrication, and Figure 11B shows an example device fabricated on a 3-inch (7.62 centimeter) wafer. Figure 11C shows bright-field optical imaging highlighting the high quality of the alternating patterned PFPE-DMA and metal lines. Figure 11D shows a scanning electron microscope (SEM) image demonstrating uniform pattern formation across the device, and Figure 11E shows a focused ion beam (FIB) cross-sectional image showing (i) no delamination from the PFPE-DMA layer and (ii) strong adhesion of the sputtered metal wiring to the PFPE-DMA layer. The conductivity of the metal electrodes was quantitatively verified by measuring the electrical resistance as a function of aspect ratio. Figure 12A shows the aspect ratio dependence of the experimentally observed resistance R. A typical aluminum / gold (40 nanometers / 100 nanometers) interconnect has a conductivity of 2.25±0.55 10 7The electrical conductivity was observed to be 0.05 S / m, comparable to the conductivity predicted using standard values. The electrode array was then separated from the fabrication substrate and subjected to a uniaxial strain of 2%, and no change in the resistance of the interconnects was observed after the application of uniaxial strain, as shown in FIG. 12B. According to certain embodiments, standard electroplating techniques were applied to coat the electrode tips with PEDOT:PSS or platinum black. FIGS. 13A-13B show the specific electrochemical impedance modulus (FIG. 13A) and phase (FIG. 13B) as a function of frequency for electrode tips with and without a PEDOT:PSS coating.
[0141] Example 8 This example shows the successful implantation of a brain probe containing perfluoroelastomer. The brain probe was synthesized as described above. FIG. 14 is a photograph of a microfabricated plastic frame used to hold the device flat while it was detached from the substrate. The microfabricated plastic frame was fabricated as described in Example 5. The microfabricated plastic frame was then removed prior to implantation. A 70 micrometer diameter tungsten shuttle with an etched tip was used to guide the perfluoroelastomer-based brain probe into mouse brain tissue. FIG. 15A is a photograph showing the implantation of a perfluoroelastomer-based brain probe into mouse brain tissue according to one embodiment. The shuttle was removed, leaving the device in the mouse brain tissue. FIG. 15B is a photograph of a freely moving mouse with a perfluoroelastomer-based brain probe implanted in each hemisphere of the brain.
[0142] A flat, flexible cable connected to the device at one end was connected to a voltage amplifier for recording electrophysiological data. Neuronal activity in freely moving mice (such as the mouse in Figure 15B) was measured at different sites on the device. A Blackrock Microsystems® Cereplex μ-headstage was connected to the flat flexible cable on the head of the mouse. A Cereplex® Direct data acquisition card and Cereplex software were used to record and filter the electrophysiological recordings. Figure 16A shows an exemplary site of the device and shows filtered signals (band pass filter 300-6000 Hz) showing burst activity on multiple electrodes recorded 3 days after implantation. Figure 16B shows a magnified view of the boxed region in Figure 16A, and Figure 16C shows a magnified view of the boxed region in Figure 16C. As shown in Figure 16C, the detected spikes were not synchronous and did not crosstalk between adjacent channels. A custom spike sorting algorithm was used to identify single neuron activity. The threshold for spike detection was set at 5 times the standard deviation of the filtered (300–6000 Hz bandpass) time series, and principal component analysis was used for dimensionality reduction. The extracted waveforms were clustered and noise artifacts were filtered out using the “kmeans” function in MATLAB. Figure 16D shows the spike sorting analysis showing the waveforms (left) and raster plots (right) of multiple neurons recorded simultaneously by such a brain probe. Meanwhile, Figure 16E shows the changes in the signal recorded by the same electrode at 1 and 2 weeks after implantation (left shows the filtered voltage recording, right shows the detected average waveform). The activity of the recorded single neurons was stable with no qualitative changes in the signal-to-noise ratio even after more than 2 weeks. The asterisks in all panels of Figure 16A-16E indicate voltage artifacts.
[0143] Example 9 This example shows the preparation of fluorinated polymer precursor solutions of the fluorinated polymers poly(1,1,1,3,3,3-hexafluoroisopropyl acrylate) (PHFIPA) and poly[2-(perfluorohexyl)ethyl]acrylate (PPFHEA). Fluorolink® MD700, a bifunctional PFPE-urethane methacrylate, was obtained from Solvay and used as the crosslinking agent. 2-hydroxy-2-methylpropiophenone was used as the photoinitiator. The monomers, crosslinker, and photoinitiator of each polymer were mixed in a weight ratio of 100 / 1 / 0.5 to prepare the spin-coating precursor solutions of PHFIPA and PPFHEA. 100-200 mJ / cm was used for crosslinking of PHFIPA and PPFHEA thin films. 2 The ultraviolet irradiation dose (wavelength 365 nm) was used.
[0144] Example 10 This example shows that fluorinated polymer (e.g., perfluoropolyether) layers have higher electrochemical impedance modulus after prolonged exposure to saline solutions. This example compares the measured decrease in specific electrochemical impedance modulus of polymers after prolonged immersion in 10x phosphate buffer solution at 65°C, similar to the tests described under these conditions in Example 4. Layers of fluorinated polymers such as poly(1,1,1,3,3,3-hexafluoroisopropyl acrylate) (PHFIPA), poly[2-(perfluorohexyl)ethyl]acrylate (PPFHEA), and PFPE-DMA are compared to layers of polydimethylsiloxane (PDMS), styrene-ethylene-butylene-styrene (H-SEBS), polyimide (PI), polyisobutylene (PIB), and SU-8 2000.5 epoxy photoresist, which serve as a comparison in this example.
[0145] Electrochemical impedance measurements were performed as described above. The polymer layers were immersed in 10x phosphate buffered saline (PBS) under rapid aging conditions at 65°C. Figure 17A plots the specific electrochemical impedance modulus (top) and phase (bottom) of the dielectric polymers under initial conditions and after immersion in 10x PBS at 65°C (t / H for PFPE-DMA, PHFIPA, PPFHEA, PDMS, H-SEBS, PI, SU-8). 2 = 5 days / micrometer 2 For PDMS, t / H 2 = 1.55 days / micrometer 2 17B and 17C show the specific electrochemical impedance modulus (H 2 17B-17C) as well as the specific electrochemical impedance modulus of the SU-8 layer decreased very slowly compared to the specific electrochemical impedance modulus of the other polymers (PIB, PI, H-SEBS, and PDMS). These data indicate that fluorinated polymers are generally long-term stable under physiological salt conditions.
[0146] Example 11 This example illustrates an exemplary method for fabricating a brain probe comprising a fluorinated polymer, such as perfluoropolyether, according to certain embodiments. The exemplary method is illustrated in FIG. 18. The method is similar to that described in Example 5 above. All photoresists and developers were obtained from MicroChem Corporation unless otherwise noted.
[0147] A 1.3-inch thermally oxidized silicon wafer (UniversityWafer) was rinsed with acetone, IPA, and water, and blow-dried. It was then dehydrated at 110 °C for 3 min and treated with O2 plasma at 100 W, 40 sccm O2 for 1 min. The bonding promoter hexamethyldisilazane (HMDS), LOR 3A photoresist, and S1805 photoresist were spin-coated at 4000 rpm / s for 1 min. The LOR 3A photoresist was hard-baked at 180 °C for 5 min, followed by application of S1805 photoresist and hard-baking at 115 °C for 1 min. The photoresist was then spin-coated at 40 mJ / cm 2 The wafer was exposed to UV light and developed with CD-26 developer for 70 seconds, then rinsed with pure water and blow-dried. A 100 nm Ni layer was then evaporated onto the wafer using a thermal evaporator, and lifted off with Remover PG for 3 hours.
[0148] 2. SU-8 2010 epoxy resin was used to form the spacers. SU-8 2010 was spin-coated onto the wafer at 3000 rpm / s for 2 min, and pre-baked at 60 °C for 2 min and 95 °C for 4 min. SU-8 2010 epoxy was applied at 170 mJ / cm 2 The resulting film was exposed to UV light for 200 s and post-baked at 60 °C for 2 min and 95 °C for 2 min 30 s. Finally, the SU-8 2010 epoxy was developed in SU-8 developer for 2 min and rinsed with IPA, then blow-dried and hard-baked at 180 °C for 1 h.
[0149] 3. The Cr / Au (15 / 100 nm) I / O pads on the brain probe were deposited by e-beam evaporation using the same lift-off technique described in step 1.
[0150] 4. The wafer was first washed with IPA, water, and blow-dried. Then, the PFPE-DMA precursor was spin-coated onto the wafer at a range of 2000-6000 rpm / s for 1 min and pre-baked at 115 °C for 2 min to obtain a film thickness ranging from 500 nm to 3 μm depending on the spin speed and precursor concentration. The spin-coated PFPE-DMA film was aligned with a photomask aligner and then irradiated with 10-30 mJ / cm using the exemplary customized nitrogen diffuser described in Example 5. 2 The PFPE-DMA was then post-baked at 115 °C for 1 min, developed in developer (1:3 volume ratio of bis(trifluoromethyl)benzene:1,1,1,3,3-pentafluorobutane) for 1 min, and blow-dried. The patterns were cleaned using O2 plasma. Finally, the PFPE-DMA patterns were hard-baked at 150 °C for 1 h.
[0151] 5. The PFPE-DMA surface was activated with plasma for 2-6 minutes at a power ranging from 20-30 W and an argon flow rate of 40 sccm.
[0152] 6. LOR3A photoresist and S1805 photoresist or S1813 photoresist were patterned on the wafer as in step 1. Different combinations of metal films, such as Al / Au, Al / Au / Al, Al / Au / Pt, Cr / Au, and Cr / Au / Cr, were deposited by sputtering, with thicknesses ranging from 20 to 100 nanometers for each layer. Finally, the metal layers were lifted off with Remover PG overnight. An airbrush gun loaded with Remover PG was used to remove the lift-off residue.
[0153] 7. PFPE-DMA was spin-coated and UV-cured, followed by plasma surface treatment, lift-off resist patterning, and metal sputtering to form an additional layer of wiring, similar to steps 4 to 6.
[0154] 8. The top PFPE-DMA layer was patterned as described in step 4.
[0155] 9. (Optional step not shown in FIG. 18). SU-8 2010 (with a thickness selected based on the total thickness of the brain probe) was used to define a framework to hold the soft brain probe during release. An exemplary plastic frame is described above in Example 8 with reference to FIG. 14.
[0156] 10. (Omitted from Figure 18.) To connect the soft brain probe to the recording setup, metal electrodes were successively deposited from the PFPE-DMA onto a silicon dioxide substrate using isotropic deposition of metal, allowing standard flip-chip bonding of a flexible cable.
[0157] Example 12 This example illustrates the properties of an exemplary brain probe fabricated using the method of Example 9. FIG. 19 shows a bright field (BF) optical image illustrating an exemplary brain probe including six layers of PFPE-DMA sandwiching four layers of exemplary metal electrodes. The inset of FIG. 19 shows the electrodes in more detail. The lateral resolution of this exemplary brain probe was approximately 1 micron for the PFPE-DMA features, and the thickness was controllable in the range of 0.3-3 microns. Focused ion beam (FIB) milling SEM of a cross-section of the exemplary brain probe showed no delamination between the PFPE-DMA and metal layers, even after uniaxial stretching to 20% elongation.
[0158] The brain probe was then chip-bonded and connected to the recording device. After chip-bonding, the electrode tip was coated with PEDOT:PSS or Pt Black using standard electroplating techniques to confirm the electrode conductivity. For electrodeposition, a Bio-logic SP-150 potentiostat and the commercial software EC-lab for voltage or current control were used. The electrode of the brain probe was connected to the working electrode. A platinum wire immersed in the precursor solution was used as the counter electrode, which also served as the voltage reference. The precursor solution for platinum black deposition consisted of 1 mM chloroplatinic acid solution and 25 mM sodium nitrate. Cyclic voltammetry was used, varying the potential from -1.0 V to 0.2 V at 0.05 V / s for 10-15 cycles. For PEDOT-PSS deposition, an electrolyte consisting of 0.01 M PEDOT (Sigma-Aldrich, USA) and 0.1 M sodium PSS (Sigma-Aldrich, USA) in water was used. The electrochemical polymerization reaction was carried out under constant voltage conditions. In the constant voltage mode, polymerization was carried out at a constant current of 1 V for 30 seconds.
[0159] Figure 20 shows the change in impedance modulus at 1 kHz before and after PEDOT:PSS and Pt black electroplating for 40 μm diameter electrodes of the brain probe (n=32, bars show mean ± SD). In all cases, P<0.0001 by two-tailed paired t-test, indicating that coating with PEDOT:PSS or platinum black caused a significant decrease in impedance and that the contacts were functioning properly.
[0160] To confirm the stability of the exemplary brain probe, the impedance of the sputtered Al / Au interconnects and Pt electrodes was measured over time. The results are shown in FIG. 21, and as shown, the exemplary brain probe did not change impedance significantly over time. The stability of the impedance of the interconnects indicates the long-term stability of the electrodes.
[0161] Measure the elastic modulus of an exemplary brain probe and determine its elastic modulus (Ed The exemplary brain probe was compared to other state-of-the-art brain probes in terms of elastic modulus (EL) and electrode number density (the number of electrodes formed per square micron of the brain probe). FIG. 22 shows a comparison of elastic modulus and electrode number density of the brain probes, with the elastic modulus of typical brain tissue shown as the shaded area. As shown in FIG. 22, the exemplary electrodes described herein had the lowest elastic modulus among all the brain probes. Furthermore, the exemplary brain probe described herein had a 100-fold higher electrode number density compared to the state-of-the-art electrodes with similar elastic modulus. The elastic modulus of the exemplary brain probe described herein was about 1000-fold lower than that of the state-of-the-art brain probes with similar electrode number density. The ratio of electrode number density to elastic modulus of the exemplary brain probe described herein was about 1000-fold lower than that of the state-of-the-art brain probes with similar electrode number density. -8 Electrode / micron 2 In contrast, the ratio of electrode number density in state-of-the-art brain probes to the elastic modulus of an exemplary brain probe is 10 -12 Electrode / micron 2 -Pa to 10 -10 Electrode / micron 2 -Pa, demonstrating that the exemplary brain probe described herein achieves both superior mechanical properties and high sensor density compared to other state-of-the-art brain probes.
[0162] Example 13 In this example, the bond energy between two exemplary layers of PFPE-DMA bonded by the method of Example 9 was measured using a 90° peel test performed at peel speeds of 0.1 mm / s, 1 mm / s, and 10 mm / s. FIG. 23 shows a schematic of the peel test, and FIG. 24 shows the bond energy between the top PFPE-DMA layer and the bottom PFPE-DMA layer, or to glass for comparison. Also shown in FIG. 24 is the fracture toughness of PFPE-DMA. As shown in FIG. 24, the self-bonding energy of the PFPE-DMA layer was approximately 100% larger than the bond energy to the glass substrate (36.0±0.5 J / m at a peel speed of 0.1 mm / s, respectively). 2 and 4.9±0.7 J / m 2 ), significantly exceeding the inherent fracture toughness of the two layers (measured at 128 J / m 2and 261 J / m 2 ), indicating that the two PFPE-DMA layers are strongly bonded and do not easily peel off under strain.
[0163] Example 14 In this example, the interconnect resistance of the exemplary brain probes was measured on the substrate and in a free-standing configuration under unstrained and uniaxial strain conditions. Figure 25 shows the interconnect resistance of each brain probe on the substrate after detaching the brain probe from the substrate and then uniaxially stretching it by 2% (λ=1.02) and 5% (λ=1.05). As shown, the interconnect resistance was consistent under all conditions and remained high even at 5% strain.
[0164] Example 15 In this example, an exemplary brain probe was modeled using finite element analysis (FEA) to understand its mechanical properties. Abaqus 6.12 software was used to analyze the mechanical properties of various polymer brain probes. The goal of the simulation is to evaluate the strain and stress concentration of a composite beam bending around a capillary of circular cross section under gravity. The brain probe was modeled with three layers, a central metal layer of 140 nm thickness sandwiched between two dielectric layers of 4.5 microns thickness with elastic modulus of PFPE-DMA or SU-8. The elements used were S4R5 or S4R, with a mesh size of 50 microns, and the probe-capillary contact was modeled with only normal forces between the surfaces (shear-free contact).
[0165] Multilayer devices encapsulated with dielectric elastomers are more flexible than devices made with plastic dielectric materials. Comparing a 9 μm-thick PFPE-DMA with an SU-8 brain probe containing a 100 nm-thick metal wiring layer (Extended Data Fig. 8a–c), the PFPE-based brain probe shows significantly higher flexibility. Finite element analysis confirmed the difference in flexibility due to the difference in elastic modulus between the elastomeric and hard dielectric materials. The metal layer becomes the primary load-bearing member, as the dielectric elastomer contributes little to the load-bearing capacity. As a result, a simple beam model shows that this design reduces the bending stiffness of the brain probe by four orders of magnitude (Extended Data Fig. 8b–d).
[0166] Further finite element analysis showed that the strain concentration in the central metal layer (~0.003) was much lower than the yield strain of Au, even when the 9 μm thick PFPE-DMA brain probe was bent by gravity around a 1 mm diameter capillary. This simulation result indicates that the metal wiring does not undergo plastic deformation or fracture when the soft brain probe is bent. The bonding of the metal wiring to the elastomer was also sufficient to generate a wrinkle pattern. This is a feature commonly observed in laminates containing islands of stiff material on a soft substrate, which can tolerate large strains before the stiff layer breaks, compared to the free-standing fracture strain. This result may further explain why the metal connections in the exemplary brain probe described herein maintained high conductivity even after 5% uniaxial strain.
[0167] Since brain probes can generally be multi-layered, a multi-layer composite model was evaluated to model multi-layers of various thicknesses. Figure 26 shows the composite beam model of a brain probe with 2N-1 layers of metal interconnects. It is assumed that layers of the same material have the same thickness. The variable h d and m are the thicknesses of the dielectric encapsulation layer and the metal layer, respectively. For the purposes of the model, the layer thickness values are h d = 2 microns, h m = 40 nm. As shown in the figure, the strain ε xxvaries throughout the composite beam. The elastic modulus and Poisson's ratio of the metal are E metal =79GPa and ν metal = 0.22. For modeling composite beams containing stiff plastics (such as SU-8), realistic estimates of the elastic modulus and Poisson's ratio are E plastic =4GPa and ν plastic = 0.33. To model a stiff composite beam containing an elastomer, the elastic modulus and Poisson's ratio are set to E elastomer = 0.5MPa and ν elastomer We chose a realistic value of =0.5.
[0168] The bending stiffness of the composite beams was estimated as a function of the number of layers in the composite beam. Figure 27 shows the results, which indicate that the bending stiffness of the stiff plastic beam is much higher than that of the elastomeric beam. As shown, as the number of metal layers increases, the bending stiffness of the elastomeric composite beam approaches the bending stiffness expected with only metal layers, indicating that the bending stiffness of the thick brain probe is limited by the bending stiffness of the metal layers rather than the bending stiffness of the polymer layers. Figure 28 shows the ratio of the bending stiffness of the stiff plastic beam to the elastomeric beam as a function of the number of metal layers. As the number of metal layers increases, the ratio of the bending stiffness of the stiff plastic composite beam to the elastomeric composite beam approaches the asymptotic limit of 0.28, which is due to the contribution of the metal layers to the bending stiffness of both composite beams.
[0169] Example 16 This example illustrates a method for transporting and aligning an exemplary brain probe using an exemplary frame of the type described in the previous example. FIG. 29A illustrates a perspective schematic of an exemplary brain probe 502 in an exemplary frame 504, according to some embodiments. Also illustrated is a shuttle 506 (in this case a tungsten shuttle) used to apply the exemplary brain probe. FIG. 29B illustrates a side view schematic of an exemplary method for inserting a brain probe. In step I, the shuttle 506 was used to insert the brain probe 502 into the brain tissue, while the frame 504 held the brain probe 502 in place. In step II, the shuttle was removed. In step III, the frame 504 was removed from the brain probe 502, which remained in the brain tissue. Finally, in step IV, dental cement 508 was applied to seal the brain probe 502 in place while allowing communication between the brain probe and the recording setup. This method allowed the exemplary brain probe of Example 12 to be implanted into the brain of a mouse. The soft probe was implanted in the somatosensory cortical region and connected via a flat flexible cable to a voltage amplifier for electrophysiological recordings, which are described in more detail below.
[0170] Example 17 This example shows the insertion of an exemplary brain probe into a mouse brain and subsequent brain activity measurements. The brain probe was inserted according to the methods described in Examples 8 and 16. Figure 30 shows representative spontaneous activity from a 16-channel PFPE-DMA one month after implantation. Data was analyzed at two-week intervals using spike sorting analysis. Figure 31 shows the results of the spike sorting analysis, showing the average waveforms of representative single-unit action potentials. Recorded activity of single units is stable over a 10-week period after implantation, with little change in waveform shape or interspike interval over the entire period. Principal component analysis (PCA) further demonstrated the stability of the brain probe, showing that all units exhibited approximately constant positions in the first and second principal component planes (PC1-PC2) from 2 to 10 weeks after implantation. This is shown in Figure 32, which shows unit positions for several channels in the PC1-PC2 planes in relation to channels and time in Figure 32.
[0171] FIG. 33A shows the noise level averaged over all channels, which remained low and fairly constant after implantation. (For n=16 electrodes, the noise was 10.4±1.8 μV at 2 weeks and 11.8±1.8 μV at 10 weeks, as shown in FIG. 33A). FIG. 33B shows the spike amplitude averaged over all channels, which increased slightly after 10 weeks, but this was primarily the result of activity in a single channel (spike amplitude was 11.8±1.8 μV). (Spike amplitude was 119.7±19.2 μV at 2 weeks and 160.6±55.3 μV at 10 weeks, n=8 units). These results indicate that the brain probe operated as intended over 10 weeks with virtually no degradation.
[0172] Finally, to examine immune responses from expandable brain probes, we examined immune responses in mice to exemplary implanted 9 micron thick PFPE-DMA and SU-8 brain probes that can incorporate at least 4-8 layers of electrodes in the mouse brain. Immunohistology of brain sections was performed 2, 6, and 12 weeks after implantation to evaluate immune response reactions to the implanted brain probes. SU-8 probes of the same dimensions were implanted as controls (n=4 mice per time point).
[0173] Immunohistochemistry and confocal fluorescence imaging were performed. At each time point (2, 6, and 12 weeks after implantation), mice were anesthetized with 40–50 mg / kg sodium pentobarbital and perfused transcardially with 40 mL of 1x PBS and 40 mL of 4% paraformaldehyde, followed by decapitation. Brains embedded with the exemplified brain probes were removed from the skull and postfixed in paraformaldehyde at 4°C for 24 h. Brains were transferred to sucrose solutions (gradually increasing concentrations from 10% to 30%, w / v) until they sank to the bottom. Samples were embedded in optimal cutting temperature (OCT) compound and cut into 30-micron-thick slices on a cryostat. Brains implanted with SU-8 brain probes of the same thickness were used for comparison.
[0174] Brain sections were first incubated with primary antibodies: NeuN (targeting neuronal nuclei, 1:200, Abcam #ab177487, USA), GFAP (targeting astrocytes, 1:200, Abcam #ab4674, USA), and IBA1 (targeting microglia, 1:100, Abcam #ab5076, USA) at 4 °C overnight. After washing three times with 1x (or 1x) PBS, brain sections were incubated with secondary antibodies for 3–4 h at room temperature. Brain slices were stained with 4',6-diaminophenylindole 8 (DAPI) for 10 min. Finally, after washing with 1x PBS, all samples were imaged with a Leica TCS SP8 confocal microscope.
[0175] Images taken 2, 6, and 12 weeks after implantation showed a significant enhancement of NeuN (neuron) signals around the PFPE-DMA probe compared to the SU-8 probe (p<0.05, n=4, two-tailed unpaired t-test). Notably, NeuN intensity increased to endogenous levels at 12 weeks after implantation (92.7±14.0% vs. 61.6±16.9%, mean±SD, n=4), indicating high biocompatibility of the PFPE-DMA probe. Fluorescence intensity of astrocytes and microglia at 12 weeks after implantation showed a significant decrease around the exemplary PFPE-DMA brain probe compared to the SU-8 probe (GFAP: 111.7±27.7% vs. 303.7±62.6%, Iba-1: 15.5±24.6% vs. 156.4±21.7%, mean±SD, n=4). These results demonstrate the high biocompatibility of the PFPE-DMA dielectric elastomer and the potential for further increased density of electrodes for long-term brain implantation.
[0176] The normalized mean fluorescence intensity of neurons (NeuN), astrocytes (GFAP), and microglia (IBA-1) as a function of distance from the probe boundary at 2, 6, and 12 weeks after implantation is reported in Figure 34. Data were normalized using the fluorescence intensity at 525-550 μm away from the probe plane. Values reported are means ± SD, n=4, * p < 0.05; ** p < 0.01; *** p<0.001, two-tailed unpaired t-test.
[0177] These results demonstrate the long-term biocompatibility and functionality of the exemplary PFPE-DMA brain probes described herein.
[0178] Although several embodiments of the invention have been described and illustrated herein, those skilled in the art can readily envision various other means and / or structures for carrying out and / or obtaining the functions and / or results and / or one or more advantages described herein, and each such variation and / or modification is deemed to be within the scope of the present invention. More generally, those skilled in the art will readily appreciate that all parameters, dimensions, materials, and configurations described herein are meant to be exemplary, and that the actual parameters, dimensions, materials, and / or configurations will depend on the particular use or application for which the teachings of the present invention are / are used. Those skilled in the art will recognize, or be able to ascertain with no more than routine experimentation, many equivalents to the specific embodiments of the invention described herein. Thus, the foregoing embodiments are presented by way of example only, and it will be understood that within the scope of the appended claims and their equivalents, the invention may be practiced otherwise than as specifically described and claimed. The present invention is directed to each individual feature, system, article, material, and / or method described herein. Furthermore, any combination of two or more such features, systems, articles, materials, and / or methods is within the scope of the present invention, provided that such features, systems, articles, materials, and / or methods are not mutually inconsistent.
[0179] The indefinite articles "a" and "an," as used in the specification and claims, unless clearly indicated to the contrary, should be understood to mean "at least one."
[0180] The term "and / or" as used herein and in the claims should be understood to mean "either or both" of the elements so conjoined, i.e., elements that are conjunctive in some cases and disjunctive in other cases. Other elements may be optionally present other than the elements specifically identified by the "and / or" clause, whether related or unrelated to the specifically identified elements, unless expressly indicated to the contrary. Thus, as a non-limiting example, a reference to "A and / or B," when used in combination with open-ended language such as "comprising," can refer to, in one embodiment, A without B (optionally including elements other than B); in another embodiment, B without A (optionally including elements other than A); in yet another embodiment, both A and B (optionally including other elements); and so forth.
[0181] As used herein and in the claims, "or" should be understood to have the same meaning as "and / or" as defined above. For example, when separating items in a list, "or" or "and / or" shall be construed to be inclusive, i.e., including at least one, but not more than one, of a number or list of elements, and optionally further including items not listed. Only terms clearly indicating the contrary, such as "only one of," "only one of," or, when used in the claims, "consisting of," refer to the inclusion of exactly one element of a number or list of elements. In general, the term "or" as used herein shall be construed to indicate exclusive alternatives (i.e., "one or the other, but not both") only when preceded by an exclusive term, such as "either," "one of," "only one of," or "exactly one of." As used in the claims, "consisting essentially of" shall have its ordinary meaning as used in the field of patent law.
[0182] As used herein and in the claims, the phrase "at least one" referring to a list of one or more elements should be understood to mean at least one element selected from any one or more elements in the list of elements, but not necessarily including at least one of each and every element specifically listed in the list of elements, and not excluding any combination of elements in the list of elements. This definition also allows that elements other than those specifically identified in the list of elements to which the phrase "at least one" refers may optionally be present, whether or not related to the specifically identified elements. Thus, as a non-limiting example, "at least one of A and B" (or, equivalently, "at least one of A or B" or, equivalently, "at least one of A and / or B") can refer, in one embodiment, to at least one, optionally one or more, A, where B is absent (and optionally including elements other than B); in another embodiment, to at least one, optionally one or more, B, where A is absent (and optionally including elements other than A); in yet another embodiment, to at least one, optionally one or more, A, and at least one, optionally one or more, B (and optionally including other elements); etc.
[0183] Some embodiments may be embodied as methods, various examples of which have been described. The acts performed as part of the methods may be ordered in any suitable manner. Thus, embodiments may be configured such that acts are performed in an order different from that shown, that different (e.g., more or fewer) acts are included than those described, and / or that some acts may be performed simultaneously, even though the acts have been shown as being performed sequentially in the specifically described embodiments above.
[0184] In the claims, the use of ordinal numbers such as "first," "second," "third," etc. to modify claim elements does not, in and of itself, imply a priority, precedence, or ordering of one claim element relative to other claim elements, or the temporal order in which acts of a method are performed, but is merely used to distinguish claim elements as a label to distinguish a claim element having a certain name from other claim elements having the same name (if an ordinal number is used).
[0185] As in the specification above, in the claims, all transitional phrases such as "comprising," "including," "carrying," "having," "containing," "involving," "holding," and the like, are understood to be open-ended, i.e., to mean an inclusion without limitation. As provided for in the United States Patent Office Manual of Patent Examining Procedure, Section 211.03, only the transitional phrases "consisting of" and "consisting essentially of" must be closed or semi-closed transitional phrases, respectively.
Claims
1. a first layer comprising a first fluorinated polymer; a second layer coupled to the first layer; and a third layer comprising a second fluorinated polymer and bonded to the second layer; Optionally, said first fluorinated polymer is the same as said second fluorinated polymer; Optionally, the first fluorinated polymer is different from the second fluorinated polymer; Optionally, said third layer has an average thickness H in microns, and the polymer in the substrate exhibits a decrease in specific electrochemical impedance modulus at 1 kHz of 50% or less after immersion in a 10x PBS solution at 65°C for a period of at least 1*H2 days; or Optionally, the polymer in the substrate exhibits a decrease in specific electrochemical impedance modulus at 1 kHz of 50% or less after immersion in a 1x PBS solution at 37°C for a period of at least 500 days.
2. 1. An article comprising a substrate adapted to be implanted into an organ of a subject, said substrate comprising a plurality of electrodes, said substrate comprising a first layer comprising a first fluorinated polymer, a second layer bonded to said first layer, and a third layer comprising a second fluorinated polymer bonded to said second layer, optionally wherein said organ is a brain.
3. 1. An article comprising a substrate including a plurality of electrodes, the substrate comprising a first layer comprising a first fluorinated polymer, a second layer bonded to the first layer, and a third layer comprising a second fluorinated polymer bonded to the second layer; The substrate is 10 6 The article has a total modulus of elasticity of less than or equal to 100 Pa.
4. The article of any one of claims 1 to 3, wherein the second layer comprises a metal or metal alloy, optionally the second layer comprises aluminum, and optionally the second layer comprises gold.
5. the first fluorinated polymer and / or the second fluorinated polymer are crosslinked; Optionally, the article further comprises one or more additional layers; Optionally, the first layer has a smallest dimension that is at least 0.3 micrometers and no greater than 3.0 micrometers; Optionally, the first fluorinated polymer and / or the second fluorinated polymer have a weight average molecular weight of greater than 20 kDa; Optionally, the first fluorinated polymer and / or the second fluorinated polymer are patterned; The article of any one of claims 1 to 3, optionally wherein the pattern of the first fluorinated polymer and / or the second fluorinated polymer has a lateral resolution of 5 micrometers or less.
6. 3. The article of claim 1 or 2, wherein the article exhibits a modulus of elasticity of less than 1 MPa.
7. the first fluoropolymer and / or the second fluoropolymer are capable of exhibiting elastic tensile deformation at or above 20% strain; Optionally, the article is part of a device; Optionally, the article is a sensor; The article of any one of claims 1 to 3, optionally wherein the article is a sensor of neural activity.
8. a first layer comprising a perfluoropolyether; a second layer bonded to the first layer; and a third layer comprising a perfluoropolyether and bonded to the second layer; Optionally, the second layer comprises a metal or metal alloy; Optionally, the second layer comprises aluminum; or Optionally, said second layer comprises gold.
9. The perfluoropolyether is crosslinked, Optionally, the article further comprises one or more additional layers; Optionally, the first layer has a smallest dimension that is at least 0.3 micrometers and no greater than 3.0 micrometers; Optionally, the perfluoropolyether has a weight average molecular weight of greater than 8 kDa; 9. The article of claim 8, optionally wherein the perfluoropolyether has a weight average molecular weight greater than 20 kDa.
10. The perfluoropolyether is patterned; Optionally, the perfluoropolyether pattern has a lateral resolution of 5 micrometers or less; or Optionally, the article exhibits a modulus of elasticity of less than 1 MPa; Optionally, the crosslinked perfluoropolyether is capable of exhibiting elastic tensile deformation at or above 20% strain; 10. The article of claim 8 or 9, optionally having an impedance greater than 50% of the impedance of the membrane before immersion.
11. 10. The article of claim 8 or 9, wherein the article is part of a device, optionally the article is a sensor, optionally the article is a sensor of neural activity.
12. An article comprising a perfluoropolyether having a weight average molecular weight of less than 8 kDa, said perfluoropolyether being present in a semiconductor substrate.
13. An article comprising a polymer comprising a crosslinked perfluoropolyether on a substrate, the polymer being formed into an article having a minimum dimension of at least 0.3 micrometers upon immersion in 1,3-bis(trifluoromethyl)benzene for a period of 9 seconds or more; When dried in nitrogen and measured at 1 kHz, it has a 6 indicates the specific electrochemical impedance modulus in Ω·m, Optionally, said smallest dimension is 3.0 micrometers or less; Optionally, the period is 30 seconds or more; or Optionally, the polymer in the substrate exhibits a decrease in specific electrochemical impedance modulus at 1 kHz of 50% or less after immersion in a phosphate buffer for 100 days; Optionally, the polymer of the substrate exhibits a decrease in specific electrochemical impedance modulus at 1 kHz of 50% or less after immersion in a phosphate buffer for 450 days; Optionally, said article has a smallest dimension of 1.0 micrometer or less.
14. 1. A plurality of electrodes on a substrate for use in insertion within an organ of a subject, said substrate comprising a first layer comprising a first fluorinated polymer, a second layer bonded to said first layer, and a third layer comprising a second fluorinated polymer bonded to said second layer, optionally wherein said organ is a brain.
15. depositing a fluorinated polymer on a substrate; applying an inert gas plasma to the fluorinated polymer to form a treated fluorinated polymer; and depositing a material onto said treated fluorinated polymer, optionally wherein said inert gas plasma comprises argon or nitrogen.
16. depositing a fluorinated polymer on a substrate; treating said fluorinated polymer to facilitate deposition; and depositing a second fluorinated polymer onto said treated fluorinated polymer, or optionally depositing a material that forms a plurality of electrodes onto said treated fluorinated polymer.
17. A plurality of electrodes on a substrate for use in determining an electrical signal, the plurality of electrodes of the substrate are at least partially contained within a target; the substrate comprises a first layer comprising a first fluorinated polymer, a second layer bonded to the first layer, and a third layer comprising a second fluorinated polymer bonded to the second layer; Optionally, the substrate has a total elastic modulus of 10 6 Pa or less and comprises a layer comprising a fluorinated polymer.
18. 1. A substrate electrode for use in determining the electrical activity of a single cell in a living subject, said substrate electrode being in contact with said cell for at least five days, said substrate comprising a layer comprising a fluorinated polymer, and optionally said cell being a neuron.
19. 1. A plurality of electrodes on a substrate for use in electrically stimulating cells in a subject, the substrate comprising: a first layer comprising a fluorinated polymer, a second layer bonded to the first layer, and a third layer comprising a fluorinated polymer bonded to the second layer.
20. depositing a perfluoropolyether onto a substrate; applying an argon plasma to the perfluoropolyether to form a treated perfluoropolyether; and depositing a material onto the treated perfluoropolyether; Optionally further comprising aligning and patterning the perfluoropolyether; The method optionally further comprising adding spacers to said substrate.